Mussel inspired tissue adhesives and methods of use thereof
By developing a bionic adhesive containing zein and a compound containing catechol or phenol, combined with iron crosslinking agent and interface crosslinking agent, the poor adhesion and toxicity of existing surgical adhesives have been solved, and an efficient and safe wound sealing effect has been achieved.
Patent Information
- Application Number
- CN202380060662.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-19
- Filing Date
- 2023-08-21
- Publication Date
- 2025-04-01
AI Technical Summary
Existing surgical adhesives have poor adhesion under bodily fluid and pressurized conditions, and have problems with toxicity and mechanical mismatch, making it difficult to effectively seal the wound.
A bionic adhesive containing zein and one or more compounds containing catechol or phenols were developed, combining iron crosslinking agents and interface crosslinking agents to form strong adhesion and biocompatible properties.
It achieves strong adhesion under body fluid and pressurized conditions, reduces the risk of toxicity, and improves the effect of wound closure, and is cost-effective.
Smart Images

Figure CN119744184A_ABST
Abstract
Description
priority
[0001] This application is related to and claims priority to U.S. Provisional Patent Application No. 63 / 399,522, filed on August 19, 2022. The contents of the foregoing application are hereby incorporated by reference into this disclosure in their entirety. Technical Field
[0002] The present disclosure relates to a biomimetic adhesive, which includes zein and one or more compounds containing catechol or gallol, and the biomimetic adhesive has excellent adhesion properties and is biocompatible. The adhesive may also include an iron crosslinking agent, an interfacial crosslinking agent, or both. A method for making and using the adhesive is also provided. Background Art
[0003] Wound leakage, either bleeding or the release of fluids and gases, is a major complication of most surgeries around the world. Traditionally, such wounds are closed using sutures, staples, and wires; however, these traditional wound closure methods are gradually being replaced by tissue sealants or adhesives because they are invasive and can cause additional complications, increasing the risk of prolonged wound closure, tissue damage, infection, and incomplete wound closure. According to the Surgical Sealants and Adhesives Global Market Report 2022 released by ReportLinker, the global surgical sealants and adhesives market is expected to grow from $2.12 billion in 2021 to $2.39 billion in 2022, at a compound annual growth rate (CAGR) of 13%. In addition, the market is expected to grow to $3.13 billion by 2026, with a CAGR of 6.9%.
[0004] There are two key requirements for an effective tissue sealant: (1) the ability to bind to tissue under conditions of body fluids and pressure (at least until the tissue regenerates), and (2) being cytocompatible and inducing minimal, if any, toxicity or foreign body response in the subject (including, for example, the ability to degrade in vivo into nontoxic byproducts). The two earliest commercially available sealants for surgical applications were fibrin-based and cyanoacrylate (butyl and octyl cyanoacrylate)-based sealants. Fibrin sealants (Tisseel, Vistaseal) TM (e.g., ) is a two-component sealant composed of fibrinogen and thrombin, which, when applied to the target site, react with each other and mimic a blood clot to seal the wound. Although these sealants initially showed promise, they have poor adhesion strength and carry the risk of disease transmission (because they are derived from pooled donated blood).
[0005] In contrast, cyanoacrylate adhesives ( Omnex, etc.) exhibit rapid gel times and immediate tissue sealing properties. However, cyanoacrylates decompose in vivo into toxic byproducts including formaldehyde and exhibit a mechanical mismatch with soft tissue, which restricts their use to strictly topical adhesive applications. These limitations of the earliest commercially available tissue sealants led to the development of albumin and glutaraldehyde-based ( PreveLeak, etc.), polyethylene glycol (Progel TM , Coseal, etc.) and polyurethane The advent of newer and improved sealants. While these newer adhesives have shown good promise, there remains a need for an effective alternative that does not have the toxicity and poor adhesion issues and is cost effective to purchase.
[0006] Natural and biomimetic materials have also gained a lot of attention in recent years. In this regard, adhesives inspired by marine organisms such as mussels, barnacles, and oysters have been studied as a source of waterproof adhesives. These marine organisms can adhere tightly to underwater surfaces while being able to withstand not only the humid and changing marine environment but also the turbulent waves. In addition, these marine organisms can remain attached to rocks for years at a time. These properties have inspired researchers to develop tissue adhesives and sealants that mimic their adhesion chemistry.
[0007] The attachment system of sea mussels is called "byssus" and is secreted from the mussel's foot and consists of multiple threads that end in adhesive plaques. The byssus is made up of approximately 25-30 different proteins, of which only 7-8 are found in plaques, and only 5 (Mytilus foot protein type 2 (mfp-2), Mytilus foot protein type 3 (mfp-3), Mytilus foot protein type 4 (mfp-4), Mytilus foot protein type 5 (mfp-5), and Mytilus foot protein type 6 (mfp-6)) are specific to plaques. One of the key components in sea mussel adhesives is a molecule called l-3,4-dihydroxyphenylalanine (DOPA), which is mainly found in mfp-3 and mfp-5.
[0008] Mussel-inspired adhesives have been synthesized using various strategies. Natural polysaccharides such as chitin, cellulose, hyaluronic acid, chitosan, silk fibroin, etc. have been modified with 3,4-dihydroxy-L-phenylalanine (L-DOPA), hydrocaffeic acid, dopamine through surface chemistry and covalent binding to develop mussel-inspired polysaccharide-based tissue adhesives. The polymer chain backbone of synthetic polymers has also been modified using dopamine or L-DOPA. Synthetic polymers such as polystyrene, polylactic acid, and polyethylene glycol have been adapted to incorporate DOPA chemistry. In addition, DOPA groups have been incorporated into recombinant protein systems through lysine and tyrosine incorporation. However, these traditional mussel-inspired adhesives can be costly and difficult to synthesize, require curing additives and other ingredients, have poor adhesion, and may have toxicity issues.
[0009] There remains a need for a natural, biodegradable, easily synthesized, scalable, and low-cost adhesive that is biocompatible, strongly adheres (even when impacted by biological fluids), and has a fast curing time. Summary of the invention
[0010] Provided is an adhesive. The adhesive may include zein and one or more compounds containing catechol or gallol. Optionally, before curing, zein accounts for 25-45 weight percent or about 25-45 weight percent (weight %, wt.%) (e.g., 25-45 weight %) of the adhesive. In certain embodiments, the adhesive also includes an interfacial crosslinker, an iron crosslinker, or both an iron crosslinker and an interfacial crosslinker. One or more compounds containing catechol or gallol may include catechol, vanillin, caffeic acid, juglone (5-hydroxy-1,4-naphthoquinone), catecholamines, resveratrol, 3,4-dihydroxyphenylacetic acid (DOPAC), catechin hydrate, 3,4-dihydroxybenzoic acid, 3,4-dihydroxybenzaldehyde, tannic acid (TA), gallic acid, gallic tannin, ellagic acid, acetic acid pyrogallol, 1,2,3-trihydroxybenzene, quercetin, gallol, or any combination thereof. The adhesive can be formulated at a neutral pH or about a neutral pH (about pH = 7). The adhesive can be formulated to have a pH of 6-8 or about 6-8 (e.g., a pH of about 5.5, a pH of about 6, a pH of about 6.5, a pH of about 7, a pH of about 7.5, a pH of about 8, or a pH of about 8.5).
[0011] When the adhesive includes an iron crosslinker, the iron crosslinker may include ferrous sulfate (FeSO4), ferric chloride (FeCl3), iron oxide nanoparticles, ferric nitrate (Fe(NO3)3), iron (III) acetylacetonate (Fe(acac)3 or Fe(C5H7O2)3), potassium ferrate (K2FeO4), or any combination thereof. When the adhesive includes an interfacial crosslinker, the interfacial crosslinker adhesive includes an interfacial crosslinker, which may include transglutaminase (TGnase) (including but not limited to microbial TGnase (mTG)), ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), N-hydroxysuccinimide (NHS), elastin-like polypeptide (ELP), polyethylene glycol (PEG), dendrimers, glutaraldehyde and / or a photocrosslinker. In certain embodiments, the interfacial crosslinker includes TA. In certain embodiments, before the adhesive is cured, zein is about 25-45 wt % (e.g., 25-45 wt %), and one or more compounds containing catechol or gallol are TA, which account for 5-30 wt % or about 5-30 wt % (e.g., 5-30 wt %). In certain embodiments, zein accounts for 40 wt % or about 40 wt % (wt %), and one or more compounds containing catechol or gallol are TA, which account for 7 wt % or about 7 wt % of the uncured adhesive. In certain embodiments, zein accounts for 26 wt % or about 26 wt %, and one or more compounds containing catechol or gallol are TA, which account for 21 wt % or about 21 wt % of the uncured adhesive. In certain embodiments, zein accounts for 26 wt % or about 26 wt %, and one or more compounds containing catechol or gallol are TA, which account for 28 wt % or about 28 wt % of the uncured adhesive. In certain embodiments, zein comprises at or about 30 wt % and the one or more catechol- or gallol-containing compounds is TA, which comprises at or about 21 wt % of the uncured adhesive.
[0012] The adhesive may also include a solvent. In certain embodiments, the solvent includes an organic solvent. In certain embodiments, the solvent includes an aqueous solvent. In certain embodiments, the solvent is both an aqueous solvent and an organic solvent. The solvent may include ethanol and water. Ethanol and water may be present in a volume ratio of (2-5): 1 or about (2-5): 1. Ethanol and water may be present in a ratio of 5: 1 or about 5: 1, 4: 1 or about 4: 1, 3: 1 or about 4: 1, or 2: 1 or about 2: 1.
[0013] The tensile strength of the adhesive can be as high as about 20 MPa.
[0014] The binder may further include at least one oxidizing agent. The binder may further include at least one filler. The at least one filler may include hydroxyapatite, calcium carbonate, calcium phosphate, magnesium phosphate, laponite, montmorillonite, or any combination thereof.
[0015] Tissue sealants are also provided. In certain embodiments, the tissue sealant includes the adhesive herein. In certain embodiments, the tissue sealant includes zein, TA, and a solvent. The solvent may include an aqueous solvent, an organic solvent, or both an aqueous solvent and an organic solvent. In certain embodiments, the solvent includes ethanol and water. In certain embodiments, the tissue sealant consists of (e.g., consists only of) zein, TA, ethanol, and water.
[0016] The tissue sealant may also include an interfacial crosslinker, an iron crosslinker, or both an interfacial crosslinker and an iron crosslinker. In certain embodiments, the interfacial crosslinker includes TGnase. TGnase may be combined with zein, TA, and a solvent, or may be applied sequentially to the target tissue with the tissue sealant.
[0017] In certain embodiments, the tissue sealant further comprises at least one filler. The at least one filler may comprise hydroxyapatite, calcium carbonate, calcium phosphate, magnesium phosphate, laponite, montmorillonite, or any combination thereof.
[0018] Also provided is a method for sealing damaged tissue of a subject (e.g., a mammal). In certain embodiments, the method includes applying an adhesive or tissue sealant as described herein to the damaged tissue. The method may also include applying an interfacial crosslinking agent to the damaged tissue to form a first layer, and applying an adhesive or tissue sealant to the first layer (e.g., injected into the damaged tissue and / or coated on the damaged tissue).
[0019] The interfacial crosslinking agent may include a viscous solution of TGnase. In certain embodiments, the viscous solution of TGnase includes TGnase and water. The interfacial crosslinking agent may include TGnase powder (e.g., applied or sprayed on damaged tissue).
[0020] In certain embodiments, the method includes forming a first layer and applying an adhesive to the first layer.
[0021] The damaged tissue may be selected from the group consisting of skin, heart tissue, stomach tissue, lung tissue, liver tissue, intestine, dura mater and aorta. In certain embodiments, the subject is a mammal. In certain embodiments, the subject is a human.
[0022] The method may also include curing the adhesive or tissue sealant. The adhesive or tissue sealant may cure in the presence of a biological fluid. The damaged tissue may be in an oral environment. In certain embodiments, the adhesive or tissue sealant is cured in saliva while the damaged tissue is in an oral environment.
[0023] The one or more catechol- or gallol-containing compounds of the adhesive can interact with functional groups of the damaged tissue to promote adhesive bonding to the damaged tissue.
[0024] The method may also include applying sutures to the damaged tissue. The method may also include applying a graft to the damaged tissue. In certain embodiments, an adhesive or tissue sealant is applied to the damaged tissue, and then the graft is applied to the damaged tissue and the adhesive or tissue sealant. In certain embodiments, the graft is applied to the damaged tissue, and then the adhesive or tissue sealant is applied to the surface of the graft and to the tissue surrounding the graft.
[0025] The method can also include curing adhesive by removing solvent or promoting to remove solvent from adhesive.Curing adhesive can include exposing adhesive or tissue sealant to oxygen or heat.Before adhesive / tissue sealant and graft are applied to damaged tissue, adhesive or tissue sealant can be applied to the graft, and it is solidified or solidified less than about 15 minutes (for example, less than 15 minutes).Before adhesive / tissue sealant and graft are applied to damaged tissue, adhesive or tissue sealant can be applied to the graft, and it is solidified less than about 40 minutes (for example, less than 40 minutes).
[0026] The volume of adhesive or tissue sealant applied may be about 80 μl to 150 μl. The volume of adhesive or tissue sealant applied may be about 10 μl to 25 ml. The volume of adhesive or tissue sealant applied may be at or about 150 μl.
[0027] A method for preparing an adhesive is provided. The method for preparing an adhesive may include: forming a first solution by combining zein, one or more catechol- or gallol-containing compounds, a solvent, and optionally an interfacial crosslinking agent, an iron crosslinking agent, or both an iron crosslinking agent and an interfacial crosslinking agent; if necessary, adjusting the pH of the first solution to at or about 6-8 (e.g., such as 6-8); and curing the first solution to substantially remove the solvent therefrom.
[0028] Curing the first solution may include incubating the first solution at about 31.0° C. to about 42.0° C. Curing the first solution may include incubating the first solution at or about 37° C. Curing the first solution may include exposing the first solution to oxygen. Curing the first solution may include photocuring.
[0029] The method may also include applying the first solution (e.g., the first solution of incubation) to the layer comprising TGnase. In certain embodiments, TGnase is a powder. In certain embodiments, TGnase is a viscous solution comprising TGnase and water. In certain embodiments, the first solution also comprises TGnase.
[0030] The one or more catechol- or gallol-containing compounds may be selected from the group consisting of TA, vanillin, gallic acid, caffeic acid, juglone, quercetin, catechin hydrate, 3,4-dihydroxybenzoic acid, and 3,4-dihydroxybenzaldehyde.
[0031] The solvent may include ethanol and water. In certain embodiments, the ratio of ethanol to water of the solvent of the first solution may be about 5:1, about 4:1, about 3:1 or about 2:1. The first solution may include one or more compounds containing catechol or gallol including TA, and the first solution may include 40% by weight or about 40% by weight of zein and 7% by weight or about 7% by weight of TA. The first solution may include one or more compounds containing catechol or gallol including TA, and the first solution may include 26% by weight or about 26% by weight of zein and 21% by weight or about 21% by weight of TA. The first solution may include one or more compounds containing catechol or gallol including TA, and the first solution may include 26% by weight or about 26% by weight of zein and 28% by weight or about 28% by weight of TA. The one or more catechol- or gallol-containing compounds of the first solution can include TA, and the first solution can include 30 wt % or about 30 wt % zein and 21 wt % or about 21 wt % TA.
[0032] In certain embodiments, the amount of one or more of zein, one or more catechol- or gallol-containing compounds, and the solvent of the first solution can be adjusted to adjust one or more properties of the adhesive (e.g., modulus, stiffness, etc.) to correspond to the mechanical properties of the target tissue.
[0033] Also provided is a kit for preparing the adhesive or tissue sealant of the present invention. The kit may include at least one of the adhesive or tissue sealant of the present invention and instructions for use. In certain embodiments, the kit includes zein, one or more compounds containing catechol or gallol, and a solvent, wherein the zein and one or more compounds containing catechol or gallol are hydrated with a solvent for immediate use. In certain embodiments, the kit includes zein, one or more compounds containing catechol or gallol, and a solvent, wherein the zein is hydrated with a solvent and stored in a first container, and one or more compounds containing catechol or gallol are stored in a second container (separate from the first container). BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In view of the following detailed description of various exemplary embodiments of the present disclosure, the embodiments disclosed herein and other features, advantages and aspects included therein and methods of achieving them will become apparent. These detailed descriptions will be better understood when combined with the accompanying drawings.
[0035] Figure 1 A schematic diagram of a burst pressure test setup used in Example 3 is shown.
[0036] Figure 2 A schematic diagram showing the test setup used to determine the long-term adhesion and stability of a sealant.
[0037] Figure 3 A graph showing the effect of ethanol to water ratio on Z40T7 lap shear strength.
[0038] Figure 4 Shown is a graph of data relating total solvent concentration to burst pressure for zein based sealant Z40T7.
[0039] Figures 5A-5C Graphical data is shown on how the ratio of zein and tannic acid (TA) concentrations in various sealant formulations affects the ultimate burst pressure strength of the sealant. The varying TA amount is limited by the final viscosity and consistency of the final formulation. Figure 5A Data are shown for the effect of varying TA concentration from 1-14 wt % at 40 wt % zein. Figure 5B Data are shown for the effect of varying TA concentration from 7-21 wt % at 30 wt % zein. Figure 5C Data are shown for the effect of varying TA concentration from 7-28 wt % at 26 wt % zein.
[0040] Fig. 6A and 6B Graphical data on the effect of adding Fe crosslinking agent on burst pressure strength of Z40T7 and Z26T21 respectively are shown.
[0041] Figures 7A-7D Figure 1 shows graphical data regarding the effect of pH on the burst pressure strength of the top 4 sealant formulations (i.e., the sealant formulations that exhibited the highest burst pressure values), each formulation being prepared at a different pH value (pH = 5, 7, and 9). Fig. 7A The data of Z40T7 is shown. Figure 7B Showing the data of Z26T21, Figure 7C Data for Z40T7+0.5 wt% Fe are shown, Fig.7D Data for Z26T21 + 0.1 wt% Fe are shown.
[0042] Figures 8A-8C Graphical data on the effect of adding three different interfacial crosslinkers (chitosan (Chi), EDC / NHS and transglutaminase (TGnase)) on the burst pressure of Z40T7 and Z26T21 are shown, where Fig. 8A A preparation with chitosan as a cross-linking agent is shown. Figure 8B The preparation with EDC / NHS as cross-linking agent is shown. Figure 8C Formulations with transglutaminase as cross-linking agent are shown.
[0043] Fig. 9 Graph showing the burst pressure of porcine skin tissue at 30 minutes and 2 hours cure time for zein based sealants, Tisseel and Superglue compared to normal abdominal pressure on the skin.
[0044] Fig.10 Graph showing the burst pressure of hog casings (processed sausage) at 30 minutes and 2 hours cure time for zein based sealants, Tisseel and Superglue compared to normal physiological pressure in sausage casing.
[0045] Fig.11 Graph showing the burst pressure of porcine heart tissue at 30 minute and 2 hour cure times for zein-based sealants, Tisseel, and Superglue compared to the normal physiological pressure of the heart (approximately normal blood pressure).
[0046] Fig.12 Graph showing the burst pressure of porcine stomach tissue at 30 minutes and 2 hours cure time for all zein based sealants, Tisseel and Superglue compared to normal physiological pressure in the stomach.
[0047] Fig.13 Graph showing the burst pressure of porcine lung tissue at 30 minutes and 2 hours cure time for all zein based sealants, Tisseel and Superglue compared to the normal physiological pressure of the lung.
[0048] Fig.14 Graph showing the burst pressure of porcine liver tissue at 30 minutes and 2 hours cure time for all zein based sealants, Tisseel and Superglue compared to normal physiological pressure of the liver.
[0049] Fig.15Shown is a graph of the burst pressure of porcine aortic tissue at 30 minutes and 2 hours cure time for all zein-based sealants, Tisseel and Superglue, compared to normal physiological pressure in the aorta (approximately normotensive blood pressure).
[0050] Fig.16A and 16B Shown is a graph of the burst pressure of porcine dural tissue (eg, dura mater) at 30 minutes and 2 hours of cure time for all zein-based sealants and Tisseel compared to normal physiological pressure in the dura mater.
[0051] Fig.17 Graph showing lap shear strength of all zein based adhesives at 30 minutes and 2 hours cure time.
[0052] Figures 18A-18C A diagram of the steps of an in vitro model of gastric tissue is shown, showing stained water leaking from a 3 mm puncture in the stomach ( Fig.18A ), Use adhesive Z40T7 to seal the puncture underwater ( Fig.18B ), and the puncture was immediately sealed without leakage after the adhesive Z40T7 was applied to the underwater puncture ( Fig. 18C ).
[0053] Figures 19A-19C This is a step diagram of the in vitro flow model of the casing, showing the continuous flow and leakage of water from a 3 mm perforation in the casing ( Fig.19A ), seal the perforation with Z40T7 ( Fig.19B ), the perforation was sealed within 10 seconds after the adhesive Z40T7 was applied without leakage ( Fig.19C ).
[0054] Fig. 20A and 20B A study was conducted to evaluate the ability of a sealant to remain adhered to tissue for an extended period of time (up to 72 hours) in a humid environment. Fig. 20A Images of casings tested with (i) Z40T7, (ii) Z40T7+Tgnase, (iii) Z26T21, and (iv) Z26T21+Tgnase are shown, while Fig. 20B Shows about Fig. 20A Shown is a graphical data of the amount of permeated PBS collected 72 hours after casing leakage.
[0055] Fig.21A and 21B The 3 mm perforations on the back of rat carcasses were Fig.21A ) and perforations sealed with Z40T7 ( Fig. 21B ) images.
[0056] Fig. 22 Graph showing the burst pressure of porcine small intestine tissue at 30 minutes and 2 hours cure time for all zein based sealants and Tisseel compared to normal physiological pressure of the small intestine.
[0057] Fig.23 is a graph of lap shear strength for various zein and TA ratios.
[0058] Fig.24 yes Fig.23 Graph of lap shear strength of the formulations identified in compared to ARTISS at 2 hours cure time.
[0059] Figures 25A-25C Shown are the results of a live / dead assay related to the cytocompatibility of cells exposed to 1X, 10X, and 100X dilutions of the filtrate, wherein Fig.25A A chart showing the results, Fig.25B An image showing the results, and Fig.25C PrestroBlue metabolism results are shown.
[0060] Fig.26 is a graph of the burst pressure of casings of Z40T7 and Z26T21 before and after gamma irradiation at 30 minutes cure time.
[0061] Fig. 27 7-day cohort wound healing images at 0, 4, and 7 days after application of Z40T7, Z40T7+sutures, Tisseel, and sutures only.
[0062] Fig.28 are images of wound healing in the 14-day group at days 0, 4, 7, 10, and 14 after administration of Z40T7, Z40T7+sutures, Tisseel, and sutures only.
[0063] Fig.29 Shown are the burst pressure values of zein adhesive on collagen casings as implants at 30 minutes of curing time.
[0064] Fig.30 Shown are the burst pressure values for zein adhesive with collagen casing as graft casing at 15 minutes curing time (adhesive coated over the entire graft material).
[0065] Fig.31 Shown are the burst pressure values of the dura mater with grafts of Z40T7+TGnase at 15 minutes of curing time (adhesive coated over the entire graft material) compared to the grafts with collagen coating.
[0066] Fig.32 Shown are the burst pressures of Z26T21 when applied directly to the dura mater or onto a graft.
[0067] Fig.33 FIG. 5 is a graph showing the effect of increasing adhesive volume when the adhesive is applied in conjunction with a graft on the dura mater at a 15 minute cure time.
[0068] Fig.34 Shown is a graph of data regarding the effect of transglutaminase on burst pressure when adhesive is applied directly to the dura mater.
[0069] Fig.35 is a data graph showing the effect of cure time on the burst pressure of an adhesive.
[0070] Fig.36 A comparative graph of data regarding the effect of perforation size on burst pressure is shown.
[0071] Fig.37 is a graph showing the lap shear adhesion strength of the dura mater combined with the graft.
[0072] Fig.38 Images showing the amount of adhesive remaining on a hydroxyapatite (HAP) substrate disc for Z40T7 and Z26T21 when studied in the presence of biofilm and PBS at two different pressure settings.
[0073] Fig.39 Shown is the effect of staining time on a bare HAP substrate (control).
[0074] Fig.40 Images showing the effect of hydrochloric acid (HCl) cleaning on HAP disk adhesion.
[0075] Fig.41 is a graph of data regarding the effects of curing in air versus curing in saliva for the zein adhesive herein coated on a limestone substrate.
[0076] Fig.42 Images showing the effect of thin versus thick coatings of zein binder on HAP coated glass substrates.
[0077] Fig.43 Images showing the effect of adding HAP powder as filler to Z26T21 on the adhesion of HAP coated glass substrate.
[0078] While the disclosure is susceptible to various modifications and alternative forms, exemplary embodiments thereof have been shown by way of example in the drawings and are herein described in detail.
[0079] While the disclosure is susceptible to various modifications and alternative forms, exemplary embodiments thereof have been shown by way of example in the drawings and are herein described in detail. DETAILED DESCRIPTION
[0080] Although the concepts of the present disclosure are elaborated and described in detail in the specification herein, the results of the specification should be regarded as illustrative rather than restrictive; it should be understood that only illustrative embodiments have been shown and described, and all changes and modifications within the spirit of the disclosure are intended to be protected.
[0081] The present disclosure generally relates to a completely biologically based biodegradable adhesive or tissue sealant that is easy to synthesize, scalable and inexpensive to produce. Some aspects of the adhesive are inspired by marine mussels; the adhesive can be based on a macromolecule (e.g., a protein or polysaccharide) and at least one compound containing catechol or gallol. As used herein, unless otherwise indicated, the terms "adhesive" and "sealant" are used interchangeably. Optionally, prior to curing, the macromolecules account for 25-45 weight percent (wt %) of the adhesive or about 25-45 weight percent (wt %) (including the endpoints of the specified range).
[0082] The macromolecule can be a protein, a polysaccharide, a synthetic polymer, a nucleic acid, or any other macromolecule that can be cross-linked with a compound containing catechol or gallol. In certain embodiments, the macromolecule is zein. In certain embodiments, the macromolecule is zein. Zein is an alcohol-soluble gluten protein present in corn or maize. Pure zein can be transparent, non-toxic, and insoluble in water. Zein is a natural degradable material with strong hydrophobicity. The amino acid sequence of naturally occurring (i.e., natural) zein is disclosed.
[0083] The protein of zein can include, but is not limited to, α-zein (e.g., having a molecular weight of about 20 to about 30 kilodaltons (kd)), β-zein (e.g., having a molecular weight of about 18 to 22 kd), γ-zein (e.g., having a molecular weight of about 25 to 35 kd), δ-zein, and / or variants (i.e., modified variants) of any of the above. In certain embodiments, the zein can be native (unmodified) zein. In certain embodiments, the molecular weight of the zein is about 15 kd.
[0084] In certain embodiments, zein can be a modified variant. "Modified variant" as used herein refers to a zein having a non-natural amino acid sequence, behaving similarly to a native zein and being soluble in alcohol. In certain embodiments, the modified variant can have about 80%, about 85%, about 90%, about 91%, about 92%, about 93%, about 94%, about 95%, about 96%, about 97%, about 98%, about 99% or about 99.5% sequence identity to the amino acid sequence of a naturally occurring (i.e., native or wild-type) zein.
[0085] "Percentage (%) of sequence identity" relative to a reference of an amino acid or polypeptide sequence is defined as the percentage of amino acid or nucleic acid residues in a candidate sequence that are identical to residues in a reference sequence, respectively, after aligning the sequences and introducing gaps (if necessary) to achieve the maximum percentage of sequence identity, and not considering any conservative substitutions as part of the sequence identity. The comparisons performed to determine the percentage of sequence identity can be implemented in various ways within the technical scope of the art, such as using publicly available computer software. For example, the percentage of identity or similarity between sequences can be determined by using the GAP program (Genetics Computer Group, software; now available online through Accelrys), and comparisons can be performed using, for example, the ClustalW algorithm (VNTI software, InforMax Inc.). In addition, a sequence database can be searched using a nucleic acid or amino acid sequence of interest. Database search algorithms are typically based on BLAST software (Altschul et al., 1990), but those skilled in the art can determine the appropriate parameters for comparing sequences, including any algorithm required to achieve the maximum comparison of the full length of the compared sequences. In some embodiments, the percentage of identity can be determined along the full length of the nucleic acid or amino acid sequence. Methods for modifying zein structural genes are well known in the art and can be used according to principles well known and understood in the art to achieve the desired modification.
[0086] The catechol or gallol containing compound can be any compound including one or more catechol or gallol moieties. Catechol includes a chemical structure having two adjacent hydroxyl (-OH) groups on a benzene ring. The catechol moiety can include the following structure: in It is the point of attachment to a compound. A gallol (or pyrogallol) moiety contains a chemical structure in which three hydroxyl (-OH) groups are attached to a benzene ring. A gallol moiety can contain the following structures: in It is the point of attachment to the compound.
[0087] Compounds containing catechol or gallol can promote crosslinking with adhesive macromolecules when cured, thereby promoting strong adhesion properties. The chemical properties of catechol and gallol are flexible, and when formulated into the compositions described herein, these parts can achieve different bonds and / or interactions with various substrates and / or compounds (through oxidation or other means) and promote crosslinking, including, for example, through the formation of hydrophobic interactions, hydrogen bonds, π-π interactions, salt bridges, etc. Therefore, catechol and / or gallol parts can easily react and / or crosslink with macromolecular parts to form adhesives herein.
[0088] In certain embodiments, the one or more catechol-containing compounds are any compounds comprising one or more catechol moieties, preferably wherein the compounds are biocompatible. In certain embodiments, the one or more catechol- or gallol-containing compounds can be catechol, vanillin, caffeic acid, juglone (5-hydroxy-1,4-naphthoquinone), catecholamines, resveratrol, 3,4-dihydroxyphenylacetic acid (DOPAC), catechin hydrate, 3,4-dihydroxybenzoic acid, 3,4-dihydroxybenzaldehyde, or any combination thereof.
[0089] In certain embodiments, one or more gallol-containing compounds are any compounds including one or more gallol moieties, preferably, wherein the compound is biocompatible. As used herein, "biocompatible" describes a substance that is substantially nontoxic in the in vivo environment of its intended use and is substantially not rejected by the patient's physiological system (i.e., non-antigenic). This can be measured by the ability of the material to pass the biocompatibility test specified in the International Standards Organization (ISO) Standard No. 10993 and / or the United States Pharmacopeia (US Pharmacopeia, USP) and / or the U.S. Food and Drug Administration (US Food and Drug Administration, FDA) Blue Book Memorandum No. G95-1, entitled "Use of International Standard ISO-10993, Biological Evaluation of Medical Devices Part-1: Evaluation and Testing". Typically, these tests measure the toxicity, infectivity, pyrogenicity, irritation potential, reactivity, hemolytic activity, carcinogenicity and / or immunogenicity of the material. Biocompatible structures or materials do not cause significant adverse reactions or responses when introduced into most patients. In certain embodiments, the one or more gallol-containing compounds include tannic acid (TA), gallic acid, gallotannin, ellagic acid, pyrogallol acetate, 1,2,3-trihydroxybenzene, quercetin, gallol, or any combination thereof.
[0090] TA is a naturally occurring polyphenol and one of the cheapest sources of mussel-inspired chemicals. TA can have the following structure:
[0091] Although TA is used in several examples herein in order to provide a complete disclosure and description of the adhesives described herein to those of ordinary skill in the art, it should be understood that the adhesives herein are not limited to TA, and other catechol- and / or gallol-containing compounds may be employed to make and use the embodiments herein.
[0092] The ring of the catechol and / or gallol moiety may be unsubstituted (except for the hydroxyl groups that constitute part of the functionality and the connection of the ring to the rest of the compound), or may be optionally substituted with other functional groups. In certain embodiments, the ring of the gallol or a compound containing catechol or gallol is substituted with an electron withdrawing group, such as a nitro group (-NO2).
[0093] The binder can be formulated at a neutral pH or about a neutral pH (eg, about pH = 7). The binder can be formulated at a pH of 6-8 or about 6-8 (eg, pH = 6-8).
[0094] The term "about" when referring to a number or value or range (including, for example, integers, fractions, and percentages) means that the number or range referred to is an approximation within experimental variability (or within statistical experimental error), so the number or range may vary between 1% and 10% of the number or range (e.g., + / - 5% to 10% of the value), provided that a person of ordinary skill in the art would consider it equivalent to the value (e.g., having the same function or result). The term "substantially" can allow for a certain degree of variability in a value or range, for example, within 90%, 95%, 99%, 99.5%, 99.9%, 99.99% or 99.999% or more of a specified value or specified limit of a range, including the specified endpoints.
[0095] In certain embodiments, the binder has a pH of 5.8, pH 5.9, pH 6.0, pH 6.1, pH 6.2, pH 6.3, pH 6.4, pH 6.5, pH 6.6, pH 6.7, pH 6.8, pH 6.9, pH 7.0, pH 7.1, pH 7.2, pH 7.3, pH 7.4, pH 7.5, pH 7.6, pH 7.7, pH 7.8, pH 7.9, pH 8.0, pH 8.1, or pH 8.2. In certain embodiments, the macromolecule and / or one or more catechol- or gallol-containing compounds or gallol-containing compounds may have an alkaline pH (e.g., up to pH 9.0 or about pH 9.0), but when combined with TA (or another acidic catechol- or gallol-containing compound or gallol-containing compound), the pH of the resulting adhesive is at or about 6, at or about 7, or at or about 8.0.
[0096] In certain embodiments, there are more macromolecules (e.g., zein) in the adhesive compared to one or more compounds containing catechol or gallol (e.g., by weight of the prepared adhesive before curing). For example, the adhesive may include 25-45 wt % or about 25-45 wt % macromolecules (e.g., zein). In certain embodiments, the adhesive includes (of the uncured adhesive) 25-45 wt % or about 25-45 wt % macromolecules (e.g., zein) and 5-30 wt % or about 5-30 wt % compounds containing catechol or gallol (e.g., TA). In certain embodiments, the adhesive may include (of the uncured adhesive) 30-40 wt % or about 30-40 wt % macromolecules (e.g., zein) and 7-10 wt % or about 7-10 wt % compounds containing catechol or gallol (e.g., TA). In certain embodiments, the adhesive comprises 40 wt % or about 40 wt % macromolecules and 7 wt % or about 7 wt % of compounds containing catechol or gallol (e.g., zein accounts for 40% of the weight of the prepared adhesive before curing, and 7% of the weight of the prepared adhesive before curing is TA). In certain embodiments, the adhesive may include (of the uncured adhesive) 24-35 wt % or about 24-35 wt % macromolecules (e.g., zein) and 18-22 wt % or about 18-22 wt % of compounds containing catechol or gallol (e.g., TA). In certain embodiments, the adhesive comprises (of the uncured adhesive) 26 wt % or about 26 wt % macromolecules and 21 wt % or about 21 wt % of compounds containing catechol or gallol. In certain embodiments, the adhesive can include at or about 25-30 wt % (of the uncured adhesive) of macromolecules (e.g., zein) and at or about 18-22 wt % of a catechol- or gallol-containing compound (e.g., TA). In certain embodiments, the adhesive includes at or about 30 wt % (of the uncured adhesive) of macromolecules and at or about 21 wt % of a catechol- or gallol-containing compound.
[0097] Alternatively, there may be more catechol- or gallol-containing compounds in the adhesive than in the macromolecules (e.g., by weight of the prepared adhesive before curing). In certain embodiments, the adhesive may include 20-30 wt % or about 20-30 wt % of macromolecules (e.g., zein) and 28-38 wt % or about 28-38 wt % of catechol- or gallol-containing compounds (e.g., TA) (of the uncured adhesive). In certain embodiments, the adhesive includes 26 wt % or about 26 wt % of macromolecules and 28 wt % or about 28 wt % of catechol- or gallol-containing compounds (of the uncured adhesive).
[0098] In certain embodiments, the binder comprises a macromolecule, at least one catechol- or gallol-containing compound, and a solvent. The macromolecule and at least one catechol- or gallol-containing compound are collectively referred to herein as the "solid component."
[0099] The solvent may be an aqueous solvent and / or an organic solvent. The solvent may include water. The solvent may include alcohol. The solvent may include alcohol and water.
[0100] The alcohol of the solvent, when used, may include ethanol, isopropanol, or any other alcohol that may be suitable for the desired use of the adhesive. In certain embodiments, the solvent is ethanol.
[0101] The components of the adhesive can be combined in appropriate proportions to produce a strong tissue sealant and / or adhesive. In certain embodiments where the solvent includes at least alcohol and water, the relative volume ratio of alcohol to water is (2-5):1 or about (2-5):1. In certain embodiments, the volume ratio of alcohol to water is 5:1 or about 5:1. In certain embodiments, the volume ratio of alcohol to water is (3-5):1 or about (3-5):1. In certain embodiments, the volume ratio of alcohol to water is (4-5):1 or about (4-5):1. In certain embodiments, the volume ratio of alcohol to water is 4:1 or about 4:1. In certain embodiments, the volume ratio of alcohol to water is (3-4):1 or about (3-4):1. In certain embodiments, the volume ratio of alcohol to water is (2-4):1 or about (2-4):1. In certain embodiments, the volume ratio of alcohol to water is 3:1 or about 3:1. In certain embodiments, the volume ratio of alcohol to water is (2-3):1 or about (2-3):1. In certain embodiments, the volume ratio of alcohol to water is 2:(1-2) or about 2:(1-2). In certain embodiments, the volume ratio of alcohol to water is 2:1 or about 2:1. In certain embodiments, the volume ratio of alcohol to water is 1:1 or about 1:1. In certain embodiments, the volume ratio of alcohol to water is 1:(2-1) or about 1:(2-1). The ratio ranges specified herein include the endpoints.
[0102] In addition, the ratio of solid component to solvent can be (45%-80%):(55%-20%) or about (45%-80%):(55%-20%) by weight of the total adhesive. The ratio can be modified as needed to ensure that the adhesive can still form a bond and / or crosslink with the substrate when applied to the substrate.
[0103] In certain embodiments, the solid component accounts for about 45% of the weight of the adhesive and the solvent accounts for about 55% of the weight of the adhesive (e.g., the weight percentage ratio of the solid component to the solvent is 45:55). In certain embodiments, the weight percentage ratio of the solid component to the solvent is 50:50 or about 50:50. In certain embodiments, the weight percentage ratio of the solid component to the solvent is 55:45 or about 55:45. In certain embodiments, the weight percentage ratio of the solid component to the solvent is 60:40 or about 60:40. In certain embodiments, the weight percentage ratio of the solid component to the solvent is 65:35 or about 65:35. In certain embodiments, the weight percentage ratio of the solid component to the solvent is 70:30 or about 70:30. In certain embodiments, the weight percentage ratio of the solid component to the solvent is 75:25 or about 75:25. In certain embodiments, the weight percentage ratio of the solid component to the solvent is 80:20 or about 80:20. The ratio ranges specified herein include the endpoints.
[0104] In certain embodiments, the weight percentage of the solid component is about 45-80 weight % of the prepared adhesive before curing. In certain embodiments, the weight percentage of the solid component is about 50-75 weight % of the prepared adhesive before curing. In certain embodiments, the weight percentage of the solid component is about 55-70 weight % of the prepared adhesive before curing. In certain embodiments, the weight percentage of the solid component is about 60-65 weight % of the prepared adhesive before curing. In certain embodiments, the weight percentage of the solid component is about 45-80 weight % (including the endpoints of the specified range) of the prepared adhesive before curing.
[0105] In certain embodiments, the weight percentage ratio of solid component to solvent is such that substantially all solid components are dissolved in the solvent (and remain dissolved when standing). In certain embodiments, the weight percentage ratio of solid component to solvent is such that most solid components are dissolved in the solvent, although some solid components can remain suspended therein. It should be understood that the higher the weight percentage of the solid component of the adhesive prepared before solidification, the greater the viscosity of the solution. Therefore, the weight percentage ratio of solid component to solvent can be modified to achieve a specific viscosity that may be beneficial to the specific use case of the adhesive.
[0106] In certain embodiments, the total weight percentage of the total solid component and the solvent accounts for at least about 90% (e.g., 90%) of the total weight of the adhesive composition before curing. In certain embodiments, the total weight percentage of the total solid component and the solvent accounts for at least about 91% (e.g., 91%) of the total weight of the adhesive composition before curing. In certain embodiments, the total weight percentage of the total solid component and the solvent accounts for at least about 92% (e.g., 92%) of the total weight of the adhesive composition before curing. In certain embodiments, the total weight percentage of the total solid component and the solvent accounts for at least about 93% (e.g., 93%) of the total weight of the adhesive composition before curing. In certain embodiments, the total weight percentage of the total solid component and the solvent accounts for at least about 94% (e.g., 94%) of the total weight of the adhesive composition before curing. In certain embodiments, the total weight percentage of the total solid component and the solvent accounts for at least about 95% (e.g., 95%) of the total weight of the adhesive composition before curing. In certain embodiments, the total weight percentage of the total solid component and the solvent accounts for at least about 96% (e.g., 96%) of the total weight of the adhesive composition before curing. In certain embodiments, the total weight percentage of total solid component and solvent accounts for at least about 97% (for example 97%) of adhesive composition total weight before curing. In certain embodiments, the total weight percentage of total solid component and solvent accounts for at least about 98% (for example 98%) of adhesive composition total weight before curing. In certain embodiments, the total weight percentage of total solid component and solvent accounts for at least about 99% (for example 99%) of adhesive composition total weight before curing. In certain embodiments, the total weight percentage of total solid component and solvent accounts for about 100% (for example, 100%) of adhesive composition total weight before curing.
[0107] In certain embodiments, adhesive comprises zein, TA and solvent (for example ethanol and water).In certain embodiments, adhesive is only made up of four kinds of components, i.e. macromolecule, compound containing catechol or gallol, ethanol and water, and does not need any additional curing agent or preservative.In certain embodiments, adhesive is only made up of four kinds of components, i.e. zein, TA, ethanol and water, and does not need any additional curing agent or preservative.In certain embodiments, adhesive can also comprise one or more fillers.The non-limiting example of this type of filler comprises hydroxyapatite, calcium carbonate, calcium phosphate, magnesium phosphate, laponite, montmorillonite or their combination.
[0108] The adhesives herein can be adjusted for specific applications (e.g., for medical and / or surgical applications, e.g., for specific tissues when used as tissue sealants). Changing the total solvent concentration, the ratio of two solvents (e.g., ethanol and water), the ratio of macromolecules to one or more compounds containing catechol or gallol, and changing the pH of the resulting adhesive can affect the properties of the resulting adhesive. For example, but not limited to, when strong bonding is required, the adhesive can be formulated with a solid component weight percentage that is higher than the solvent weight percentage. Alternatively, when a thinner adhesive is required, the adhesive can be formulated with a solid component weight percentage that is lower than the solvent weight percentage.
[0109] In certain embodiments, the adhesive may further include an iron crosslinking agent, an interfacial crosslinking agent, or both an iron crosslinking agent and an interfacial crosslinking agent.
[0110] Iron crosslinking agents may include compounds containing iron atoms and may be used to promote crosslinking and / or bridging between macromolecules of the adhesive and one or more compounds containing catechol or gallol and / or the underlying substrate to which the adhesive is applied. In certain embodiments, the iron crosslinking agent includes iron in the 3+ oxidation state. In certain embodiments, the iron crosslinking agent includes ferrous sulfate (FeSO4), ferric chloride (FeCl3), iron oxide nanoparticles, ferric nitrate (Fe(NO3)3), iron (III) acetylacetonate (Fe(acac)3 or Fe(C5H7O2)3), potassium ferrate (K2FeO4), or any combination thereof. Interfacial crosslinking agents may include non-toxic enzymes or other molecules that can catalyze the formation of covalent bonds between proteins, resulting in crosslinking. The interfacial crosslinking agent may include transglutaminase (TGnase) (including but not limited to microbial TGnase (mTG)), ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), N-hydroxysuccinimide (NHS), elastin-like polypeptide (ELP), polyethylene glycol (PEG), dendrimers, glutaraldehyde and / or a photocrosslinker. In certain embodiments, the interfacial crosslinking agent includes TA.
[0111] TGnase is an enzyme that plays a role in various biological processes, especially in the formation of covalent bonds between proteins. For example, in nature, TGnase mainly catalyzes the formation of isopeptide bonds between the γ-carboxamide group of the side chain of glutamine residues and the ε-amino group of the side chain of lysine residues, followed by the release of ammonia.
[0112] Tgnase is found in various organisms, including humans and microorganisms. For example, TGnase can include plant, recombinant animal or microorganism-derived TGnase. In certain embodiments, TGnase can be from one or more of Streptoverticillium Baldaccii, Streptomyces Hygroscopicus strain or Escherichia coli. In certain embodiments, TGnase is any type of calcium-dependent or non-calcium-dependent TGnase. In certain embodiments, the interfacial crosslinker includes one or more synthetic polymer sequences with TGnase crosslinking site characteristics.
[0113] In certain embodiments, the pH value of TGnase is in the range of about 5 to about 8. The specified pH range includes endpoints. TGnase can be a pharmaceutically acceptable salt, a hydrate, an N-oxide and / or a solvate of TGnase. The term "solvate" refers to a protein or a salt thereof, which also includes a stoichiometric or non-stoichiometric solvent bound by non-covalent intermolecular forces. When the solvent is water, the solvate is a hydrate. It should be understood that in various physical forms of TGnase, certain functional groups, such as groups such as hydroxyl, amino, can form complexes and / or coordination compounds with water and / or various solvents.
[0114] TGnase can be commercial food grade TGnase, which is advantageous when, for example, adhesive is used as a medical sealant. When adhesive is used as a medical / surgical sealant, TGnase can catalyze the reaction between the glutamine residues in zein and the lysine residues on the target tissue (e.g., damaged or impaired tissue). Therefore, TGnase can act as an interfacial crosslinking agent, which is bound to the macromolecules of the adhesive and the impaired tissue itself, thereby enhancing the adhesion strength. This combination of macromolecules (e.g., zein), compounds containing catechol or gallol (e.g., TA) and TGnase and the interaction of tissues can enhance the overall adhesion strength of the sealant in use. Other known iron crosslinking agents and / or interfacial crosslinking agents can also be used together with adhesives to achieve the same or similar effects as described herein.
[0115] The interfacial crosslinking agent may optionally be in a composition comprising at least one other substance, such as a stabilizer or filler. Non-limiting examples of such materials include maltodextrin, hydrolyzed skim milk protein or any other protein substance, sodium chloride, trisodium phosphate, sodium caseinate or lactose, hydroxyapatite, calcium carbonate, calcium phosphate, magnesium phosphate, laponite, montmorillonite or a combination thereof.
[0116] In some embodiments, the adhesive may further include an oxidant. The oxidant may include sodium periodate, tetrabutylammonium periodate, potassium permanganate, di-tert-butyl peroxide, hydrogen peroxide, cumene hydroperoxide, 2-butanone hydroperoxide, chromate, dichromate, or any combination thereof.
[0117] In certain embodiments, when measuring on aluminum substrate under similar conditions, this adhesive is as strong as commercial cyanoacrylate (Super Glue).In certain embodiments, the adhesion strength / value of adhesive (for example, during solidification) is about 1.5-2.0MPa, about 2.0-3.0MPa, 3.0-4.0MPa, about 4.0-5.0MPa, about 5.0-6.0MPa, about 6.0-7.0MPa, about 6.5-7.0MPa, about 7.0-7.5MPa, about 7.5-8.0MPa, about 8.0-8.5MPa, about 8.5-9.0MPa, about 9.0-9.5MPa, about 9.5-10.0MPa, about 10-15MPa, about 15-20MPa, about 20-21MPa or greater than about 21MPa.In certain embodiments, the tensile strength of adhesive is up to about 20MPa (for example 20MPa). In certain embodiments, the adhesive has an adhesion value of about 1.5 MPa. In certain embodiments, the adhesive has an adhesion value of about 3.0 MPa. The adhesive may also exhibit good water resistance.
[0118] Tissue sealants are also provided, which include biologically acceptable, optionally rapidly gelling (e.g., when the adhesive includes an iron crosslinker and / or an interfacial crosslinker and / or an oxidant) formulation having a specified range of adhesion and cohesion. The tissue sealants herein typically rapidly gel and / or bind when in contact with a tissue (e.g., a tissue containing collagen or other proteins). The tissue sealant may include zein, TA, and a solvent. In certain embodiments, the solvent includes ethanol and water. The tissue sealant may include any adhesive described herein. The tissue sealant may be composed of zein, tannic acid, and a solvent (and no other substantial components). The tissue sealant may also include TGnase or another crosslinker. The tissue sealant may also include an iron crosslinker and / or an interfacial crosslinker. The tissue sealant may also include an oxidant. The tissue sealant may also include a filler.
[0119] Tissue sealants may be suitable for treating tissue damage. The tissue may be any tissue type, including but not limited to skin, cardiac tissue, dura mater, gastric tissue, lung tissue, liver tissue, bone and / or cartilage, intestine, vascular tissue, aortic tissue, lymphatic tissue, muscle tissue, connective tissue, etc. Tissue sealants may be suitable for treating soft tissue lesions. Tissue sealants may be suitable for treating injured or traumatic cartilage, bone and / or cartilage-bone defects. Tissue sealants may be suitable for treating any type of biological tissue. In certain embodiments, tissue sealants may be sprayed onto lymph nodes or areas of transected lymphatic vessels. Tissue sealants may be suitable for treating neural tissue.
[0120] In certain embodiments, tissue sealants may be used for applications such as sealing tissue injuries (e.g., wounds or lacerations), reinforcing surgical sutures and / or surgical staples, adhering and / or reinforcing grafts, and / or any type of sealant and / or adhesive activity.
[0121] When applied to various tissue substrates (e.g., organs), the adhesives and tissue sealants can withstand pressures above the normal physiological pressures experienced by most tested organs (see examples below). The adhesives and tissue sealants herein also perform better than the commercial gold standard fibrin tissue sealant (Tisseel) when tested on most tissues.
[0122] When oxidized, one or more catechol- or gallol-containing compounds in the adhesive / tissue sealant of the present invention can react with functional groups in macromolecules (e.g., proteins of zein) to form a cross-linked tissue sealant. In addition, uncross-linked catechol- or gallol-containing compounds (such as TA) can further interact with functional groups of the tissue itself. Functional groups from amino acid residues in proteins, peptides, and fatty acids on tissue are the main source of covalent interactions between tissue and adhesive / sealants. Basic amino acids such as lysine, histidine, and peptides present in tissue provide amino groups while acidic amino acids such as glutamic acid and fatty acids present in tissue provide carboxyl groups to bind to relevant functional groups of the sealant (such as hydroxyl groups of the catechol- or gallol-containing compounds in the adhesive). In addition, other functional groups such as imidazole from histidine and thiol from cysteine can also bind to relevant functional groups on the sealant. Amines are the most widely targeted functional groups to date due to their greater abundance and reactivity. Other functional groups on the graft and tissue can also be cross-linked with the adhesive, including but not limited to sulfonic acid groups and phosphate groups (which can interact with the catechol and gallol moieties through coordination bonds) and hydroxyl groups (which can interact with the catechol and gallol moieties to form hydrogen bonds).
[0123] For example, the gallol groups in TA can be oxidized to quinones, which can react with amines on target tissues (e.g., damaged tissues) through various pathways. The benzene rings of quinones can react with amines, thiols, or imidazoles on tissues via Michael addition reactions. Quinones can form Schiff base linkages between carbonyl groups and amines. Most of these interactions are based on Michael-type additions. In addition, physical crosslinking via hydrogen bonding also occurs and can be an important factor in contributing to at least short-term adhesion.
[0124] A method for sealing damaged tissue of a subject is also provided. In certain embodiments, the method includes applying the adhesive or tissue sealant herein to damaged tissue (e.g., the target site of damaged tissue). The damaged tissue can be any tissue to which the adhesive or tissue sealant can be appropriately applied. The damaged tissue can be mammalian tissue. The damaged tissue can be in vivo tissue (e.g., because the adhesive and / or tissue sealant can be biodegradable, it is suitable for such applications). The damaged tissue can be any type of in vivo mammalian tissue. The damaged tissue can be in an oral environment (e.g., in the mouth of a subject).
[0125] The damaged tissue may be selected from the group consisting of casing / intestines, skin, cardiac tissue, gastric tissue, lung tissue, neural tissue, liver tissue, dura mater, and aorta. The damaged tissue may have any injury, including, for example, a puncture, wound, abrasion, cut, or any other tissue injury, where the application of a sealant / adhesive may be beneficial. The adhesive / sealant may be used to help prevent, for example, leakage (e.g., in the event that the damaged tissue is compressed), reduce blood loss, and / or be used in conjunction with or in place of mechanical methods such as suturing or stapling.
[0126] In certain embodiments, the method may further include applying an iron crosslinker and / or an interfacial crosslinker to the damaged tissue to form a first layer, and applying an adhesive to the first layer. The iron crosslinker may include a compound containing an iron atom, and may be used to promote crosslinking and / or bridging between macromolecules of the adhesive or tissue sealant and one or more compounds containing catechol or gallol, and / or the underlying tissue to which the adhesive is applied. In certain embodiments, the iron crosslinker includes iron in a 3+ oxidation state. In certain embodiments, the iron crosslinker includes ferrous sulfate (FeSO4), ferric chloride (FeCl3), iron oxide nanoparticles, ferric nitrate (Fe(NO3)3), iron (III) acetylacetonate (Fe(acac)3 or Fe(C5H7O2)3), potassium ferrate (K2FeO4), or any combination thereof.
[0127] The interfacial crosslinker can include a non-toxic enzyme or other molecule that can catalyze the formation of covalent bonds between proteins, resulting in crosslinking. The interfacial crosslinker can include TGnase (including but not limited to mTG), ELP, PEG, dendrimers, glutaraldehyde and / or a photocrosslinker. In certain embodiments, the interfacial crosslinker includes TA.
[0128] The interfacial crosslinking agent may be a powder. The interfacial crosslinking agent may be a viscous solution. The viscous solution of the interfacial crosslinking agent may include, for example, the interfacial crosslinking agent and water.
[0129] A "subject" can be a mammal. For example, but not limited to, a subject can be a human patient, a laboratory animal, such as a rodent (e.g., a mouse, rat, or hamster), a rabbit, a monkey, a chimpanzee, a domestic animal, such as a dog, a cat, or a rabbit, an agricultural animal, such as a cow, a horse, a pig, a sheep, or a goat, or a captive wild animal, such as a bear, a panda, a lion, a tiger, a leopard, an elephant, a zebra, a giraffe, a gorilla, a dolphin, or a whale. The terms "subject" and "patient" are used interchangeably herein.
[0130] In certain embodiments of the method, when the adhesive or tissue sealant is applied to the damaged tissue, the one or more catechol- or gallol-containing compounds interact with functional groups of the damaged tissue to further promote and / or support adhesive bonding to the damaged tissue.
[0131] The method may also include applying one or more sutures to the damaged tissue. The method may also include applying a graft to the damaged tissue. The graft may be a synthetic material and / or a biomaterial known in the art. In certain embodiments, the graft includes a tissue grown alone or a treated tissue patch, a growth scaffold, etc. The graft may be a porous graft (e.g., a mesh graft, such as a hernia mesh), a thin-walled graft, a xenograft, a full-thickness graft, or any other graft for replacing damaged or diseased tissue to enhance function and / or improve aesthetics.
[0132] Adhesive or tissue sealant can be applied to damaged tissue as required before or after suturing and / or transplanting.In certain embodiments, adhesive or tissue sealant is applied to the graft, then the graft comprising adhesive or tissue sealant is applied to the damaged tissue.In certain embodiments, adhesive or tissue sealant is applied to the damaged tissue before the graft is applied to the damaged tissue (for example, the graft can be applied to the damaged tissue having applied adhesive or sealant thereon).In certain embodiments, the graft is applied to the damaged tissue, then a layer of adhesive or tissue sealant is applied on the non-organization-oriented surface of the graft and on the tissue around the graft.In such embodiments, adhesive or tissue sealant do not need to be directly applied to the damaged tissue position, but can be used for the placement position (placement) of the graft to be adhered (and / or reinforced) on the damaged tissue.
[0133] The method may also include curing adhesive or tissue sealant and / or curing adhesive or tissue sealant. Adhesive or tissue sealant will solidify after removing solvent, which causes oxidation of the hydroxyl functional group of the compound containing catechol or gallol, thereby causing adhesive components to crosslink each other and / or crosslink with underlying tissue and / or graft. Solvent can be removed from adhesive or tissue sealant by exposing adhesive to oxygen. Solvent can be removed from adhesive or tissue sealant by exposing adhesive to heat. In certain embodiments, curing adhesive or tissue sealant includes removing solvent from adhesive or tissue sealant or promoting to remove solvent. Curing adhesive may include exposing adhesive or tissue sealant to oxygen and / or heat.
[0134] Applying heat to the adhesive or tissue sealant in combination with or in lieu of oxygen exposure can reduce the time required for the adhesive to cure because it can promote the evaporation or removal of the solvent therein. In certain embodiments, applying heat to cure the adhesive or tissue sealant includes exposing the adhesive or tissue sealant to a temperature of about 31.0°C to about 42.0°C (e.g., incubating the adhesive or tissue sealant at 31.0°C to 42.0°C). This temperature range is roughly consistent with body temperature and / or skin temperature (i.e., 87.8°F to 104°F), and therefore, can be used in cases where the adhesive is applied in vivo. In certain embodiments, curing the adhesive includes exposing the adhesive or tissue sealant to a temperature of about 32.0°C (e.g., 32.0°C). In certain embodiments, curing the adhesive includes exposing the adhesive or tissue sealant to a temperature of about 33.0°C (e.g., 33.0°C). In certain embodiments, curing the adhesive includes exposing the adhesive or tissue sealant to a temperature of about 34.0°C (e.g., 34.0°C). In certain embodiments, curing the adhesive comprises exposing the adhesive or tissue sealant to a temperature of about 35.0°C (e.g., 35.0°C). In certain embodiments, curing the adhesive comprises exposing the adhesive or tissue sealant to a temperature of about 36.0°C (e.g., 36.0°C). In certain embodiments, curing the adhesive comprises exposing the adhesive or tissue sealant to a temperature of about 37.0°C (e.g., 37.0°C). In certain embodiments, curing the adhesive comprises exposing the adhesive or tissue sealant to a temperature of about 38.0°C (e.g., 38.0°C). In certain embodiments, curing the adhesive comprises exposing the adhesive or tissue sealant to a temperature of about 39.0°C (e.g., 39.0°C). In certain embodiments, curing the adhesive comprises exposing the adhesive or tissue sealant to a temperature of about 40.0°C (e.g., 40.0°C). In certain embodiments, curing the adhesive comprises exposing the adhesive or tissue sealant to a temperature of about 41.0°C (e.g., 41.0°C). In certain embodiments, curing the adhesive comprises exposing the adhesive or tissue sealant to a temperature of about 42.0° C. (eg, 42.0° C.) The temperature ranges described herein are inclusive of the endpoints described therein.
[0135] In certain embodiments, when the adhesive includes a photocrosslinker or photoinitiator filler, the adhesive may be cured by applying light to the adhesive, for example, using methods known in the art.
[0136] The adhesive and / or tissue sealant herein can solidify in an in vivo environment, for example, when subjected to the influence of one or more biological fluids. In certain embodiments, the adhesive or tissue sealant can solidify in the presence of a biological fluid. The biological fluid can be any mammalian biological fluid. The biological fluid can be gastric juice. The biological fluid can be blood, plasma or serum. The biological fluid can be bile. The biological fluid can be tears. The biological fluid can be interstitial fluid. The biological fluid can be sweat. The term "biological fluid" can also include a mixture of biological fluids, such as sweat and blood, or bile and interstitial fluid. In certain embodiments, for example, when the damaged tissue is in an oral environment, the method includes allowing the adhesive or tissue sealant to solidify in saliva.
[0137] In certain embodiments, the adhesive or tissue sealant is applied to the graft before the adhesive or tissue sealant is applied to the damaged tissue, and the method may also include curing (at least partially curing) the adhesive or tissue sealant applied to the graft before the adhesive / tissue sealant and the graft are applied to the damaged tissue. In certain embodiments, the adhesive / tissue sealant is cured (e.g., exposed to oxygen, heat, and / or light) for less than about 15 minutes (e.g., less than 15 minutes) before the adhesive or tissue sealant and the graft are applied to the damaged tissue. In certain embodiments, the adhesive / tissue sealant is cured for less than about 40 minutes (e.g., less than 40 minutes) before the adhesive or tissue sealant and the graft are applied to the damaged tissue.
[0138] The adhesive and / or tissue sealant may cure in less than 15 minutes. The adhesive and / or tissue sealant may cure in less than 13 minutes, less than 12 minutes, less than 11 minutes, less than 10 minutes, less than 9 minutes, less than 8 minutes, less than 7 minutes, less than 6 minutes, less than 5 minutes, less than 4 minutes, less than 3 minutes, less than 2 minutes, and / or less than 1 minute.
[0139] Any volume of adhesive or tissue sealant can be used, as long as it can be suitable for a particular application and / or meet the needs. In certain embodiments, the amount of the volume of the adhesive or tissue sealant applied to damaged tissue is about 10 μl to 25 ml (e.g., 10 μl to about 25 ml, about 10 μl to 25 ml, or 10 μl-25 ml). In certain embodiments, for example, when used for small nerve repair, the amount of the adhesive or tissue sealant applied to damaged tissue is 10 μl or about 10 μl. In certain embodiments, for example, when used for large tissue patch repair, the amount of the adhesive or tissue sealant applied to damaged tissue is 25 ml or about 25 ml. In certain embodiments, the amount of the volume of the adhesive or tissue sealant applied to damaged tissue is 80 μl to 150 μl or about 80 μl to 150 μl. In certain embodiments, the amount of the volume of the adhesive or tissue sealant applied to damaged tissue is 150 μl or about 150 μl.
[0140] Also provided is a method for preparing an adhesive / tissue sealant. The method may include: forming a first solution by combining a first amount of zein, a second amount of one or more compounds containing catechol or gallol (e.g., TA, etc.), and a third amount of a solvent; if necessary, adjusting the pH of the first solution to about 6-8 (e.g., 6-8); and curing the first solution to substantially remove the solvent therefrom. Curing the first solution may include incubating the first solution at a temperature of about 31.0°C to 42.0°C (e.g., 31.0, 32.0°C, 33.0°C, 34.0°C, 35.0°C, 36.0°C, 37.0°C, 38.0°C, 39.0°C, 40.0°C, 41.0°C, or 42.0°C). In certain embodiments, curing the first solution includes exposing the first solution to oxygen. In certain embodiments, curing the first solution includes photocuring. Photocuring or curing with light generally refers to applying light to the adhesive or tissue sealant to provide a light-curing wavelength configured to cure the adhesive or tissue sealant (e.g., using a light emitting diode (LED), a quartz-tungsten-halogen (QTH) bulb, or another activating light source). When the first solution includes a photocrosslinker or photoinitiator filler, for example, such a filler can be photosensitive and, when irradiated with light, can promote crosslinking of the components of the first solution and / or the damaged tissue.
[0141] If desired, the pH of the first solution can be adjusted to at or about 6.0, at or about 6.5, at or about 7.0, at or about 7.5, or at or about 8.0.
[0142] The solvent may include water. The solvent may include alcohol. The solvent may include alcohol and water. The alcohol of the solvent may include ethanol, isopropanol or any other alcohol that may be suitable for the desired use of the adhesive when used. In certain embodiments, the solvent is ethanol. In certain embodiments, the ratio of ethanol to water of the first solution is 3:1 or about 3:1 or any other ratio described herein.
[0143] In certain embodiments, the first solution may further include an iron crosslinking agent, an interfacial crosslinking agent, or both an iron crosslinking agent and an interfacial crosslinking agent. The interfacial crosslinking agent may be TGnase. In certain embodiments, the first solution may further include a filler. In certain embodiments, the first solution may further include an oxidant.
[0144] One or more catechol- or gallol-containing compounds can be any catechol- or gallol-containing compound described herein. In certain embodiments, the catechol- or gallol-containing compound comprises catechol, vanillin, caffeic acid, juglone (5-hydroxy-1,4-naphthoquinone), catecholamines, resveratrol, DOPAC, catechin hydrate, 3,4-dihydroxybenzoic acid, 3,4-dihydroxybenzaldehyde, TA, gallic acid, gallic tannin, ellagic acid, pyrogallol acetate, 1,2,3-trihydroxybenzene, quercetin, gallol, or any combination thereof.
[0145] The method may also include applying the first solution of incubation to a second solution layer including an interfacial crosslinking agent. For example, the second solution may include TGnase (e.g., as a powder or as a viscous solution including TGnase and a solvent such as water). TGnase may be commercial food grade TGnase. In certain embodiments, the second solution includes a viscous solution of TGnase and a solvent (e.g., water). TGnase may be any TGnase described herein.
[0146] The first solution may include any adhesive as described herein. The first solution may include 25-45 wt % or about 25-45 wt % of zein and 5-30 wt % or about 5-30 wt % of a compound (e.g., TA) containing catechol or gallol. In certain embodiments, the first solution may include 30-40 wt % or about 30-40 wt % of zein and 7-10 wt % or about 7-10 wt % of a compound (e.g., TA) containing catechol or gallol. In certain embodiments, the first solution may include 40 wt % or about 40 wt % of zein and 7 wt % or about 7 wt % of a compound (e.g., TA) containing catechol or gallol. In certain embodiments, the first solution may include 24-35 wt % or about 24-35 wt % of zein and 18-22 wt % or about 18-22 wt % of a compound (e.g., TA) containing catechol or gallol. In certain embodiments, the first solution comprises 26 wt % or about 26 wt % zein and 21 wt % or about 21 wt % of a catechol- or gallol-containing compound. In certain embodiments, the first solution comprises 25-30 wt % or about 25-30 wt % zein and 18-22 wt % or about 18-22 wt % of a catechol- or gallol-containing compound (e.g., TA). In certain embodiments, the first solution comprises 30 wt % or about 30 wt % zein and 21 wt % or about 21 wt % of a catechol- or gallol-containing compound.
[0147] Alternatively, there may be more catechol- or gallol-containing compounds in the first solution than in zein (e.g., by weight of the prepared adhesive before curing). In certain embodiments, the first solution includes 20-30 wt % or about 20-30 wt % zein and 28-38 wt % or about 28-38 wt % of a catechol or gallol compound (e.g., TA). In certain embodiments, the first solution includes 26 wt % or about 26 wt % zein and 28 wt % or about 28 wt % of a catechol or gallol compound. The percentages of the components of the first solution may be any other percentages described herein.
[0148] The first solution may also include TGnase or another interfacial crosslinking agent, an iron crosslinking agent, or both an interfacial crosslinking agent and an iron crosslinking agent.
[0149] In certain embodiments, when the solvent of the first solution includes at least alcohol and water, the relative volume ratio of alcohol and water is (2-5):1 or about (2-5):1. In certain embodiments, the volume ratio of alcohol and water is 5:1 or about 5:1. In certain embodiments, the volume ratio of alcohol and water is (3-5):1 or about (3-5):1. In certain embodiments, the volume ratio of alcohol and water is (4-5):1 or about (4-5):1. In certain embodiments, the volume ratio of alcohol and water is 4:1 or about 4:1. In certain embodiments, the volume ratio of alcohol and water is (3-4):1 or about (3-4):1. In certain embodiments, the volume ratio of alcohol and water is (2-4):1 or about (2-4):1. In certain embodiments, the volume ratio of alcohol and water is 3:1 or about 3:1. In certain embodiments, the volume ratio of alcohol and water is (2-3):1 or about (2-3):1. In certain embodiments, the volume ratio of alcohol to water is 2:(1-2) or about 2:(1-2). In certain embodiments, the volume ratio of alcohol to water is 2:1 or about 2:1. In certain embodiments, the volume ratio of alcohol to water is 1:1 or about 1:1. In certain embodiments, the volume ratio of alcohol to water is 1:(2-1) or about 1:(2-1). The ratio ranges specified herein include the endpoints.
[0150] In addition, the ratio of the solid component to the solvent of the first solution can be (45%-80%): (55%-20%) or about (45%-80%): (55%-20%) (based on the total weight of the first solution). This ratio can be modified as needed so that the resulting adhesive can form a bond and / or crosslink with the substrate when applied to the substrate.
[0151] In certain embodiments, the solid component of the first solution accounts for about 45% of the weight of the first solution, and the solvent accounts for about 55% of the weight of the first solution (e.g., the weight percentage ratio of the solid component to the solvent is 45:55). In certain embodiments, the weight percentage ratio of the solid component to the solvent is 50:50 or about 50:50. In certain embodiments, the weight percentage ratio of the solid component to the solvent is 55:45 or about 55:45. In certain embodiments, the weight percentage ratio of the solid component to the solvent is 60:40 or about 60:40. In certain embodiments, the weight percentage ratio of the solid component to the solvent is 65:35 or about 65:35. In certain embodiments, the weight percentage ratio of the solid component to the solvent is 70:30 or about 70:30. In certain embodiments, the weight percentage ratio of the solid component to the solvent is 75:25 or about 75:25. In certain embodiments, the weight percentage ratio of the solid component to the solvent is 80:20 or about 80:20. The ratio ranges specified herein include the endpoints.
[0152] In certain embodiments, the weight percentage of the solid component accounts for about 45-80 weight % of the first solution prepared before solidification. In certain embodiments, the weight percentage of the solid component accounts for about 50-75 weight % of the first solution prepared before solidification. In certain embodiments, the weight percentage of the solid component accounts for about 55-70 weight % of the first solution prepared before solidification. In certain embodiments, the weight percentage of the solid component accounts for about 60-65 weight % of the first solution prepared before solidification. In certain embodiments, the weight percentage of the solid component accounts for about 45-80 weight % (including the endpoints of the specified range) of the first solution prepared before solidification.
[0153] In certain embodiments, the weight percentage ratio of solid components to solvent is such that substantially all solid components are dissolved in the solvent (and remain dissolved when stationary). In certain embodiments, the weight percentage ratio of solid components to solvent is such that most solid components are dissolved in the solvent, although some solid components may remain suspended therein. It is understood that the higher the weight percentage of the solid components of the first solution prepared before solidification, the greater the viscosity of the solution. Therefore, the weight percentage ratio of solid components to solvent can be modified to achieve a specific viscosity of the first solution that may be beneficial to a particular application.
[0154] In certain embodiments, the total weight percentage of the total solid components and solvents accounts for at least about 90% (e.g., 90%) of the total weight of the first solution before solidification. In certain embodiments, the total weight percentage of the total solid components and solvents accounts for at least about 91% (e.g., 91%) of the total weight of the first solution before solidification. In certain embodiments, the total weight percentage of the total solid components and solvents accounts for at least about 92% (e.g., 92%) of the total weight of the first solution before solidification. In certain embodiments, the total weight percentage of the total solid components and solvents accounts for at least about 93% (e.g., 93%) of the total weight of the first solution before solidification. In certain embodiments, the total weight percentage of the total solid components and solvents accounts for at least about 94% (e.g., 94%) of the total weight of the first solution before solidification. In certain embodiments, the total weight percentage of the total solid components and solvents accounts for at least about 95% (e.g., 95%) of the total weight of the first solution before solidification. In certain embodiments, the total weight percentage of the total solid components and solvents accounts for at least about 96% (e.g., 96%) of the total weight of the first solution before solidification. In certain embodiments, the total weight percentage of the total solid components and the solvent accounts for at least about 97% (e.g., 97%) of the total weight of the first solution composition before solidification. In certain embodiments, the total weight percentage of the total solid components and the solvent accounts for at least about 98% (e.g., 98%) of the total weight of the first solution before solidification. In certain embodiments, the total weight percentage of the total solid components and the solvent accounts for at least about 99% (e.g., 99%) of the total weight of the first solution before solidification. In certain embodiments, the total weight percentage of the total solid components and the solvent accounts for about 100% (e.g., 100%) of the total weight of the first solution before solidification.
[0155] The resulting adhesives and tissue sealants have various properties (e.g., modulus, hardness, etc.). In certain embodiments, the method may further include adjusting the amounts and / or ratios of the components of the first solution (e.g., the amounts of one or more of zein, TA, ethanol, and water) to tailor the properties of the adhesive to correspond to the mechanical properties of the target tissue.
[0156] Also provided are kits for preparing the disclosed adhesives or tissue sealants. In some embodiments, the kit includes at least one of the adhesives or tissue sealants described herein and instructions for use. "Instructions for use" as used herein refers to a publication, record, chart, or any other medium of expression used to convey the usefulness of the adhesive or tissue sealant for one of the purposes described herein. For example, the explanatory materials of the kit can be attached to a container including the adhesive and / or tissue sealant of the present invention and / or its components, or transported together with a container including the adhesive and / or tissue sealant and / or its components. Alternatively, the explanatory materials can be transported separately from the container, or provided in an electronically accessible form on an Internet website, intended to enable the recipient to use the explanatory materials in conjunction with the adhesive or tissue sealant.
[0157] In certain embodiments, the kit includes a macromolecule, one or more catechol- or gallol-containing compounds, a solvent (e.g., a solvent for any adhesive or tissue sealant described herein), and instructions for use. In certain embodiments, the macromolecule and one or more catechol- or gallol-containing compounds are hydrated by the solvent for immediate use, such as in a syringe device or vial. There, after the adhesive or tissue sealant component (i.e., the first solution) is loaded into the syringe device or vial, oxygen can be purged from the syringe device or vial.
[0158] In certain embodiments, the macromolecule and one or more catechol- or gallol-containing compounds are hydrated in a solvent for immediate use, such as in a dual syringe device to form a precursor liquid that rapidly gels upon exposure to oxygen and / or heat.
[0159] In certain embodiments, the kit includes one or more catechol or gallol-containing compounds, macromolecules, or both catechol or gallol-containing compounds and macromolecules in powder form. The different components in powder form can be stored in separate vials or containers separately from other components of adhesives or tissue sealants. The solvent can be stored in a separate vial or container. The amount of each component can be measured to achieve the desired ratio and / or viscosity and / or characteristics of the adhesive or tissue sealant. In certain embodiments, the macromolecule is hydrated with the solvent, such as in a vial or other container, and the compound containing catechol or gallol is contained in a separate vial or container. In such embodiments, the pH of the macromolecule and solvent solution can be as high as 9, especially when the compound containing catechol or gallol includes TA, which, when mixed with the macromolecule and solvent mixture, will play a role in reducing the pH of the first solution to 6 to 8 or about 6 to about 8. In certain embodiments, TA is added to the macromolecule and solvent mixture to reduce the pH of the first solution to about 7 (i.e., neutral pH).
[0160] The shelf life of the kit is about 18 months. As used herein, "shelf life" refers to the length of time that adhesive, tissue sealant and / or its components can be stored without becoming unsuitable for use or sale and / or unable to effectively show adhesion properties. In certain embodiments, the shelf life of the kit is about 17 months. In certain embodiments, the shelf life of the kit is about 16 months. In certain embodiments, the shelf life of the kit is about 15 months. In certain embodiments, the shelf life of the kit is about 14 months. In certain embodiments, the shelf life of the kit is about 13 months. In certain embodiments, the shelf life of the kit is about 12 months. In certain embodiments, the shelf life of the kit is about 11 months.
[0161] Overview
[0162] All patents, patent application publications, journal articles, textbooks, and other publications mentioned in the specification are indicative of the levels of skill of those skilled in the art to which the present disclosure pertains.
[0163] In the above description, numerous specific details are set forth in order to provide a comprehensive understanding of the present disclosure. The specific examples may be implemented without some or all of these specific details, and it should be understood that the present disclosure is not limited to a specific biological system, a specific cancer, or a specific organ or tissue, which, of course, may vary but remain applicable in view of the data provided herein.
[0164] In addition, various techniques and mechanisms of the present disclosure sometimes describe a connection or link between two components. Unless otherwise specified or the context clearly indicates the difference, words such as attached, linked, coupled, connected, and similar terms with their inflectional morphemes are used interchangeably. These words and expressions do not necessarily mean direct connection, but include connections through intermediate components. It should be noted that a connection between two components does not necessarily mean a direct, unimpeded connection, as various other components may exist between the two components. Therefore, unless otherwise specified, a connection does not necessarily mean a direct, unimpeded connection.
[0165] In addition, it should be understood that the present disclosure is presented in this manner for illustrative purposes only, and the principles and embodiments described herein can be applied to compounds and / or composition components having configurations other than those specifically described herein. In fact, it is clearly contemplated that the components of the adhesive of the present disclosure can be customized to facilitate its desired application.
[0166] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those of ordinary skill in the art. The terms and expressions used are used as descriptive terms, not limiting terms. In this regard, if certain terms are defined, described or discussed elsewhere in the "Detailed Description", all such definitions, descriptions and discussions are intended to be attributed to these terms. The use of these terms and expressions is also not intended to exclude any equivalents of the features shown and described or parts thereof. In addition, although subheadings such as "certain definitions" are used in the "Detailed Description", such use is only for ease of reference and is not intended to limit any disclosure in a certain part to that part; on the contrary, any disclosure under a subheading is intended to constitute the disclosure under each and every other subheading.
[0167] Although any methods and materials similar or equivalent to those described herein can be used in the practice or testing of the present subject matter, the preferred methods and materials are described herein.
[0168] When ranges are used herein for physical properties (eg, weight percent) or chemical properties (eg, chemical formula), all combinations and subcombinations of ranges and specific embodiments therein are intended to be included, and each range includes the endpoints.
[0169] It should be appreciated that various modifications may be made within the scope of the present disclosure. Therefore, although the present disclosure has been specifically disclosed in the context of preferred embodiments and optional features, those skilled in the art may make modifications and variations to the concepts disclosed herein. Such modifications and variations are considered to be within the scope of the present disclosure claimed herein.
[0170] When describing representative embodiments, the present disclosure may have presented the method and / or process as a specific order of steps. Insofar as the method or process does not rely on the specific order of steps described herein, the method or process should not be limited to the specific order of steps described. As will be appreciated by those of ordinary skill in the art, other orders of steps are also possible. Therefore, the specific order of steps disclosed herein should not be interpreted as a limitation on the claims. In addition, claims for methods and / or processes should not be limited to performing their steps in the order written, and those skilled in the art can easily understand that the order can be changed and still be within the spirit and scope of the present disclosure.
[0171] Some definitions
[0172] The present disclosure can be properly implemented in the absence of any elements or limitations not specifically disclosed herein. Thus, for example, any of the terms "comprising," "consisting essentially of," and "consisting of" (and related terms such as "including," "having") herein can be replaced with other referenced terms.
[0173] Likewise, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to "the method" includes one or more such methods and / or steps that have been described and / or will become apparent to one of ordinary skill in the art upon reading this disclosure. The term "substantially" can allow for a certain degree of variation in a value or range, for example, within 90%, 95%, or 99% of a stated value or a stated range limit. Example
[0174] The following examples serve to illustrate the present disclosure. The examples are not intended to limit the scope of the claimed invention. Material
[0175] Zein (molecular weight: 19-22 kDa), tannic acid and iron (III) chloride (FeCl3.6H2O) were purchased from Sigma-Aldrich (St. Louis, MO). Ethanol (190 degrees) was purchased from Decon Laboratories Inc. (King of Prussia, PA). RM transglutaminase (MooGloo TM ) were purchased from commercial sources. Unless otherwise stated, all other reagents used were purchased from Thermo Fischer Scientific (Waltham, MA). All porcine tissues and organs used in this study were purchased locally or from Animal Technologies Inc. (Tyler, TX).
[0176] For the study of the optimized zein sealant, porcine skin tissue was prepared similarly to the method and affixed to aluminum adherents. Specifically, 40 μl of sealant was applied to each tissue and bonded in a lap shear configuration. The adherents were cured in a humidifier at a temperature of 37° C. for 30 minutes and 2 hours as described above. For a 30-minute cure time, the adherents were cured in a humidifier for 20 minutes and then equilibrated at room temperature for 10 minutes. Example 1 Synthesis of a tissue sealant inspired by marine mussels
[0177] To determine the formulation with the highest adhesion strength, the concentration of zein was kept constant at 40 wt%, 30 wt%, and 26 wt%. The tannic acid concentration was varied from 1 wt% to 28 wt%. When the iron crosslinker was added, the concentration of FeCl3·6H2O was varied from 0.05 wt% to 1 wt%. The ratio of ethanol to water was kept constant at 3:1.
[0178] To prepare the sealant, all components in predetermined amounts were mixed manually using a wooden spatula. The pH of the prepared sealant was adjusted to pH 7 using 10 M NaOH solution. The sealant was then incubated at 37 °C for 24 hours to remove all air bubbles before testing. The prepared sealant was initially amber in color, but the color deepened to dark brown after 24 hours depending on the amount of tannic acid or cross-linking agent used. Example 2 Lap Shear Method
[0179] The lap shear test is performed according to a modified version of the American Society of Testing and Materials (ASTM) standard F2255-05 described above. Standard Test Method for Strength Properties of Tissue Adhesives in Lap-Shear by Tension Loading, ASTM International Website (publicly available; last accessed on August 16, 2023); Matos-Perez et al., Polymer Composition and Substrate Influences on the Adhesive Bonding of a Biomimetic, Cross-Linking Polymer, J Am Chemical Society 134(22):9498-9505(2012). The lap shear measurement is an adhesion strength test in which a sealant or adhesive formulation is applied to overlapping tissue sheets, cured, and then the force to pull the sheets apart is measured. The test can reflect both adhesive bonding and cohesive bonding.
[0180] Porcine skin tissues obtained from a butcher were cut into approximately 1.8 cm x 1.2 cm sizes. They were then fixed to aluminum attachments using cyanoacrylate glue. The glue was allowed to dry for 24 hours, and then the samples were immersed in phosphate buffered saline (PBS) for 24 hours to hydrate the porcine tissue samples.
[0181] Before applying the sealant, the tissue was blotted dry with a paper towel. For preliminary studies to optimize the ethanol to water ratio, 50 μl of sealant was applied to one of the tissue substrates and the other substrate was immediately placed on top. The attachment was cured in a humidifier at 37°C for 2 hours; specifically, it was cured in a humidifier for 1.5 hours and then kept at room temperature for 30 minutes to equilibrate. A lead block of approximately 40 grams was applied to the attachment to apply pressure during the curing process. Example 3 Burst Pressure Method
[0182] The burst pressure of the sealant was tested on a porcine tissue substrate using an in-house developed burst pressure test apparatus based on a slightly modified version of the ASTM standard (F2392-04). Standard Test Method for Burst Strength of Surgical Sealants, ASTM International Website (publicly available; last accessed on August 16, 2023). The tissue substrate was cut into approximately 2.5 cm × 2.5 cm dimensions. A biopsy punch was used to create a puncture of approximately 3 mm diameter in the center of the tissue substrate. The substrate with the sealant was then loaded onto the test fixture ( Figure 1 The test fluid was pumped into the test fixture at a rate of 5 ml / min using a syringe pump. A pressure sensor (PX409-100GUSBH, OMEGA Engineering, Norwalk, CT) connected to a computer was used to record the burst pressure.
[0183] Initial studies were conducted on porcine skin tissue using 20 μl of sealant to determine the optimal sealant formulation. The sealant was cured in a humidifier at 37°C for 2 hours. Once the optimal formulation was determined, 40 μl of sealant was applied to study the burst pressure strength of all tissue substrates. Curing was performed in a humidifier at 37°C for 30 minutes and 2 hours. For the 30-minute cure time, the samples were cured in a humidifier for 20 minutes and then equilibrated at room temperature for 10 minutes. For the remaining 2-hour cure time, the samples were cured in a humidifier for 1.5 hours and then equilibrated at room temperature for the remaining 30 minutes.
[0184] For all initial studies of all interfacial crosslinkers, 20 μl of interfacial crosslinker solution was first applied to the tissue followed by 20 μl of sealant. Once the optimal interfacial crosslinker was determined, further studies were performed by applying 40 μl of crosslinker followed by 40 μl of sealant. For all tissues, the test fluid used was PBS, except for gastric and lung tissues, where simulated gastric fluid and air were used, respectively. Example 4 Effect of the ratio of ethanol to water on lap shear strength
[0185] Zein is only partially soluble in water or ethanol; however, a combination of water and ethanol in the proper ratio can completely dissolve zein. The ratio of ethanol to water was varied to determine its effect on the final adhesion strength of one of the sealants (Z40T7).
[0186] Figure 3The lap shear strength of sealant Z40T7 at three different ethanol to water ratios (2:1, 2.5:1 and 3:1) is shown to be 4.54 ± 2.12 KPa, 5.45 ± 3.05 KPa and 10.29 ± 3.16 KPa respectively. Adhesion failure was observed at all tested ratios. Adhesion strength increased with increasing ethanol concentration. Therefore, a 3:1 ethanol to water ratio was used in all further studies. Example 5 Effects of Zein and Tannic Acid Concentrations on Burst Pressure Strength
[0187] The concentrations of zein, tannic acid (TA), ethanol, and water were selected based on previous studies. To determine the optimal zein and TA concentrations for the sealant, different sealant formulations were tested with zein concentrations varying from 40 wt%, 30 wt%, and 26 wt%, while for each zein concentration, the TA concentration varied from 1 wt% to 28 wt%.
[0188] The TA concentration range studied for each zein concentration was limited by the final viscosity and consistency of the sealant. If the final consistency after mixing all ingredients was considered to be very viscous (i.e., not pipettable) or had a watery consistency, that particular formulation was not studied further.
[0189] like Figure 5A As shown, at a zein concentration of 40 wt%, the burst pressure strength was initially proportional to the TA concentration. The highest value obtained with 7 wt% TA was 1.58 ± 0.68 psi, and the lowest value obtained with 1 wt% TA was 0.64 ± 0.30 psi. However, when the TA concentration was further increased to 14 wt%, the burst pressure strength dropped to 1.25 ± 0.68 psi. In all cases, the sealant exhibited adhesive failure.
[0190] When the concentration of zein was 30 wt%, the burst pressure value decreased with the increase of TA concentration ( Figure 5B ). The highest value of 1.21±1.13 psi was obtained at a TA concentration of 7 wt%, while when the TA concentration was reduced to 14 wt% and 21 wt%, the burst pressure values decreased to 1.03±0.21 psi and 0.74±0.35 psi, respectively. In all cases, the sealant exhibited adhesive failure.
[0191] like Figure 5CAs shown, at a zein concentration of 26 wt%, the burst pressure values obtained for 7 wt%, 14 wt%, 21 wt% and 28 wt% TA were 0.63 ± 0.46 psi, 0.69 ± 0.17 psi, 2.14 ± 0.16 psi and 1.16 ± 0.23 psi, respectively. The formulation containing 21 wt% TA not only had the highest burst pressure strength, but the failure mechanism was also cohesive. All other formulations showed adhesive failure.
[0192] Two formulations, Z40T7 (Zein 40 wt%, TA 7 wt%) and Z26T21 (Zein 26 wt%, TA 21 wt%), were selected for further study because they exhibited the best performance of the formulations tested in the burst pressure experiments. Example 6 Effect of adding iron cross-linking agent on bursting pressure strength
[0193] Transition metals such as iron (Fe) are known to form complexes with catechol and oxidize it to the quinone form, thereby further covalently cross-linking to the substrate. Fig. 6A The effect of adding a Fe crosslinker at concentrations of 0.05 wt% to 1 wt% to sealant Z40T7 on the burst pressure strength of the sealant is shown. The burst pressure strengths of Z40T7 with 0.05 wt%, 0.1 wt%, 0.5 wt%, and 1 wt% Fe crosslinker added were 1.20 ± 0.46 psi, 0.46 ± 0.21 psi, 1.22 ± 0.42, and 0.81 ± 0.59 psi, respectively. These values are lower than the formulation without any Fe crosslinker (1.58 ± 0.68 psi).
[0194] Figure 6B The effect of adding a Fe crosslinker in concentrations ranging from 0.05 wt% to 0.5 wt% in sealant Z26T21 is shown. The burst pressure strengths of sealant Z26T21 with 0.05 wt%, 0.1 wt%, and 0.5 wt% Fe crosslinker additions were 0.42 ± 0.23 psi, 1.19 ± 0.29 psi, and 0.66 ± 0.19 psi, respectively. These results are similar to those obtained with Z40T7, with no significant improvement in burst pressure values observed over the Z26T21 formulation without the Fe crosslinker (2.14 ± 0.16 psi).
[0195] Adding even the smallest amount of Fe crosslinker to the adhesive formulation resulted in a decrease in the burst pressure strength of the sealant. All sealants with added Fe crosslinker exhibited adhesive failure. Example 7 Effect of pH value on bursting pressure
[0196] Among the formulations studied, those that exhibited the highest burst pressure strength (e.g., Z40T7, Z26T21, Z40T7+0.5 wt % Fe, and Z26T21+0.1 wt % Fe) were studied at three pH values of 5, 7, and 9 to evaluate the effect of pH on the ultimate burst pressure strength of the sealant.
[0197] For Z40T7, the burst pressure strengths at pH values of 5, 7, and 9 were 0.88±0.64psi, 1.58±0.68psi, and 1.03±0.21psi, respectively. Fig. 7A For Z26T21, the burst pressure strengths at pH values of 5, 7, and 9 were 1.37±0.51psi, 2.14±0.16psi, and 0.52±0.28psi, respectively. Figure 7B ). Z40T7 exhibited adhesive failure at all pH values; however, Z26T21 exhibited cohesive failure at neutral pH and adhesive failure at all other pH values.
[0198] When 0.5 wt% Fe crosslinker was added to Z40T7, the burst pressure strengths at pH values of 5, 7, and 9 were 0.36±0.15 psi, 1.22±0.42 psi, and 0.54±0.16 psi, respectively. Figure 7C When 0.1 wt% Fe crosslinker was added to Z40T7, the burst pressure strengths at pH values of 5, 7, and 9 were 0.80±0.18 psi, 1.19±0.29 psi, and 0.72±0.18 psi, respectively ( Fig.7D ). After adding the Fe crosslinker, both sealants showed adhesive failure at all pH values.
[0199] All formulations performed best at neutral pH (pH = 7), which is exactly the physiological pH and supports that the sealants developed in this study can be expected to have similar efficiency in vivo. Example 8 Effect of introducing interface cross-linking agent on burst strength
[0200] To further increase the burst pressure of the sealant, three interfacial crosslinkers were investigated. Each of the three crosslinkers was rationally chosen and had a different crosslinking mechanism with the tissue and the sealant. Initially, chitosan was chosen due to its cationic nature.
[0201] Cheung et al., Chitosan: An Update on Potential Biomedical and Pharmaceutical Applications. Marine Drugs 13(8): 5156-5186 (2015). Due to the presence of anionic proteoglycans, tissues in vivo are in anionic state. It is expected that chitosan will enhance adhesion strength through electrostatic interactions with tissues and sealants.
[0202] A 10 mg / ml chitosan viscous solution was prepared and the pH was adjusted to 6 with acetic acid. Fig. 8A As shown, using chitosan as a cross-linking agent resulted in a decrease in the burst pressure of Z40T7 from 1.58±0.68 psi to 0.51±0.41 psi, and a decrease in the burst pressure of Z26T21 from 2.14±0.16 psi to 0.47±0.30 psi. All samples experienced adhesive failure.
[0203] In addition, carbodiimide chemistry using ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) as interfacial crosslinkers was investigated. EDC / NHS is known to be a zero-length crosslinker (i.e., it does not incorporate into macromolecules after crosslinking) and has been widely used in tissue engineering applications. Therefore, it was hypothesized that its addition to the sealant formulation would promote the formation of amide bonds between the zein-based sealant and the various carboxyl and hydroxyl functional groups of the tissue.
[0204] A 20 mg / ml EDC / NHS solution (equal parts w / w) was used for the study. Figure 8B As shown, EDC / NHS does not promote crosslinking of the sealant to the tissue. The burst pressure strength of Z40T7 decreased from 1.58±0.68psi to 0.49±0.18psi, and the burst pressure strength of Z26T21 decreased from 2.14±0.16psi to 0.79±0.42psi. All samples showed adhesive failure.
[0205] Finally, the role of commercial food-grade transglutaminase (TGnase) as a potential interfacial crosslinker was investigated. TGnase is known to help catalyze the formation of isopeptide bonds between the γ-carboxamide group of glutamine and the ε-amino group of lysine. TGnase is widely used to bind different proteins together and to bind proteins to non-protein molecules with desired functional groups such as hyaluronic acid. Here, it was hypothesized that TGnase would help bind proteins in zein to proteins and functional groups on tissues.
[0206] TGnase viscous solution was prepared by mixing 500 mg of transglutaminase with 1200 μl of deionized water (DI), and the prepared solution was used immediately. Figure 8C The use of TGnase as a cross-linker increased the burst pressure of Z40T7 from 1.58±0.68psi to 2.51±0.64psi and that of Z26T21 from 2.14±0.16psi to 2.49±0.54psi.
[0207] Z26T21 (which exhibited cohesive failure when used alone) also exhibited cohesive failure even when TGnase was used as the interfacial crosslinker. In addition, all samples containing Z40T7 and Z40T7+TGnase exhibited adhesive failure. Therefore, TGnase was determined to be the interfacial crosslinker of choice and was used in all further studies. Example 9 In vitro studies: porcine stomach and intestine casings
[0208] In vivo, body fluids and stomach contents interfere with the sealing and curing process. Therefore, in vitro experiments were performed using porcine stomach tissue (Figure 18) and sausage casings (Figure 19) to demonstrate the effectiveness of the sealant in blocking tissue leak perforations. Understandably, the sausage casings are prepared from the small intestine and therefore react similarly.
[0209] A fixed in vitro model was designed to investigate the tissue sealing ability of the sealant under physiological conditions. Briefly, a porcine stomach was filled with water dyed with a red dye. The stomach was then placed under water and a hole was punctured with a 3 mm biopsy punch, allowing the dyed water to flow through the perforation. The sealant was loaded into a syringe and incubated at 70 °C for 24 hours to partially remove some of the solvent. The sealant was then applied to the perforation on the underwater stomach. After sealing the perforation, the stomach tissue was carefully transferred to a new jar of water to test if there was any leakage from the sealed perforation.
[0210] As shown in Figure 18, when a 3 mm perforation was introduced in the gastric tissue, the dyed water leaked from the perforation. After sealing the perforation with Z40T7 under wet conditions underwater, a seal was formed immediately and no further leakage was detected. Z26T21 also sealed the perforation immediately underwater. The sealant containing TGnase could not be studied in this case because TGnase would dissolve immediately underwater.
[0211] The ability of the sealants to seal actively leaking perforations under pressure was also tested using an in vitro flow model. The flow model was designed using a casing in which water continuously flowed through it at a pressure of 0.6 psi (higher than the normal physiological pressure in the intestine). More specifically, the casing was cut into appropriate lengths and connected to a water pump that continuously circulated water through the casing at a pressure of 0.6 psi. Figures 19A-19CAs shown, a 3 mm perforation was made using a biopsy punch ( Fig.19A ). Apply the prepared glue Z40T7 to the leaking puncture for 10 seconds while applying slight pressure ( Fig.19B ). Record the pressure changes before and after the seal is pierced.
[0212] After applying adhesive Z40T7, the puncture stopped leaking and was sealed immediately ( Fig.19C ). After 1 hour the seal was still intact.
[0213] Z26T21, Z26T21+TGnase, and Z40T7+TGnase were also tested according to this method (ie, applied to the leaking puncture for 10 seconds with gentle pressure). Z26T21+TGnase and Z40T7+TGnase failed to seal the puncture immediately. Example 10 In vitro studies: long-term adhesion studies in a humid environment
[0214] Tissue sealants must seal the tissue and prevent any body fluids from leaking out of the tissue, at least until new tissue begins to regenerate. Therefore, the ability of the sealants to maintain contact with the tissue for a long period of time in the presence of body fluids was examined ( Figure 2 Briefly, casings were applied to the mouth of a 20 ml vial containing 4 ml PBS using a zip tie. A 3 mm hole was punctured and 100 μl of various sealants were applied to seal the puncture. The vial was then inverted so that the PBS pooled on top of the sealant and casing and mounted on top of a 50 ml Eppendorf tube of known weight ( Fig. 20A ). The entire assembly was sealed in a Styrofoam box and placed on a shaker at 40 rpm in an incubator at 37°C. A large container of water was used to create a humid environment in the Styrofoam box. After 72 hours, the assembly was removed and the weight of the liquid collected in the Eppendorf tube was analyzed. A control experiment was performed without perforations and sealants in the casing.
[0215] After 72 hours, 2 of 3 replicates of Adhesive Z40T7, 2 of 3 replicates of Adhesive Z40T7+TGnase and Adhesive Z26T21, and all 3 replicates of Adhesive Z26T21+TGnase were still in contact with tissue ( Fig. 20B). The casings are permeable, causing some PBS to leak into the container below. Therefore, a control experiment with no perforations or sealants was designed to determine if the amount of PBS that permeated from the casings without perforations was similar to that of the casings that were perforated and sealed with sealants. Only those samples in which the sealants remained intact after 72 hours were included in the calculations. It was found that in the samples in which the sealants remained intact, the amount of leaked PBS collected after 72 hours was similar to the amount leaked from the control experiment. Embodiment 11 In vitro study: tissue closure capacity of local wounds
[0216] The tissue sealing ability of the sealants was investigated in an in vitro full-thickness skin defect model of rat cadavers to evaluate the efficacy of the sealants on localized cutaneous wounds. The hair on the backs of euthanized rats (used for different studies) was shaved using a trimmer. A 3 mm puncture ( Fig.21A The Z40T7 and Z26T21 sealants were pre-cured in 3 ml syringes at 70 °C for 24 h. The prepared sealants were dispensed into the wound site using an 18G blunt-tip needle ( Fig. 21B Shown is Z40T7 applied to the perforation). Allow sealant to dry for 5 minutes.
[0217] Sealant Z40T7 adhered firmly to the rat skin and the hair remaining on the skin and would not fall off even when the skin was pulled with tweezers. Example 12 Burst pressure intensity on different tissue substrates
[0218] skin
[0219] Fig. 9 Shown are the burst pressures of all zein-based tissue sealants on porcine skin tissue at two different cure times (30 minutes and 2 hours) compared to commercially available fibrin-based tissue sealants (Tisseel) and cyanoacrylate glue (Superglue). The graph also shows normal physiological pressures in the abdomen.
[0220] When the curing time increased from 30 minutes to 2 hours, the burst pressure of Z40T7 increased from 1.66±0.43psi to 4.12±1.71psi. Similarly, for Z40T7+TGnase, the burst pressures at 30 minutes and 2 hours of curing time were 1.85±0.37psi and 4.01±2.06psi, respectively. The burst pressures of Z26T21 at 30 minutes and 2 hours of curing time were 1.77±1.11psi and 2.67±0.37psi, respectively. The burst pressures of Z26T21+TGnase at 30 minutes and 2 hours of curing time were 2.71±1.1psi and 3.74±1.07psi, respectively. In comparison, the burst pressures of Tisseel at 30 minutes and 2 hours of cure time were 2.87 ± 0.92 psi and 2.53 ± 0.62 psi, respectively, while the burst pressures of Superglue at 30 minutes and 2 hours of cure time were 12.04 ± 2.39 psi and 9.85 ± 5.36 psi, respectively.
[0221] like Fig. 9As shown, all zein-based sealants tested outperformed Tisseel. Of all the sealants tested, only Z26T21 and Z26T21+TGnase exhibited cohesive failure within a 2-hour cure time. Furthermore, the normal pressure in the human abdomen is approximately 0.29 psi, which is much less than the value for the zein-based sealants studied, even at a short cure time of 30 minutes. Rooban et al., Comparing Intra-Abdominal Pressures in Different Body Positions via a Urinary Catheter and Nasogastric Tube: A Pilot Study, Annals Intensive Care 2(Suppl 1): 1–7.(2012);Hamoud et al., Gastric and Urinary Bladder Pressures Correlate with Intra-Abdominal Pressure in Patients with Morbid Obesity, J Clinical Monitoring & Computing 36: 1021-1028(2022);de Keulenaer et al., What Is Normal Intra-Abdominal Pressure and How Is It Affected by Positioning, Body Mass and Positive End-Expiratory Pressure? , Intensive Care Medicine 35(6): 969–976(2009). The highest burst pressure obtained among the zein-based adhesives was Z40T7.
[0222] casings
[0223] Fig.10The burst pressure data of all the sealants studied on the casings at two different curing times are shown. The burst pressures of Z40T7 at 30 minutes and 2 hours of curing time are 1.63 ± 0.47 psi and 4.35 ± 2.65 psi, respectively. The burst pressures of Z40T7 + TGnase at 30 minutes and 2 hours of curing time are 1.68 ± 0.9 psi and 3.33 ± 1.81 psi, respectively. The burst pressures of Z26T21 at 30 minutes and 2 hours of curing time are 1.18 ± 0.27 psi and 3.13 ± 0.57 psi, respectively. The burst pressures of Z26T21 + TGnase at 30 minutes and 2 hours of curing time are 1.12 ± 0.12 psi and 1.19 ± 0.69 psi, respectively. The burst pressures of Tisseel at 30 minutes and 2 hours of curing time are 0.07 ± 0.06 psi and 0.29 ± 0.24 psi, respectively. The burst pressure of Superglue at 30 minutes and 2 hours of curing time was 3.89 ± 0.49 psi and 3.83 ± 1.38 psi, respectively.
[0224] At both curing times, all tested zein-based sealants performed better than Tisseel on casings. Among the tested sealants, three zein-based adhesives (i.e., Z40T7, Z26T21, and Z26T21+TGnase) exhibited cohesive failure at 2 hours of curing. In addition, the normal pressure in the human small intestine is about 0.38 psi, which is much smaller than the value of the tested zein-based sealants, even at a short curing time of 30 minutes. Scott et al., The Nocturnal Jejunal Migrating Motor Complex: Defining Normal Ranges by Study of 51 Healthy Adult Volunteers and Meta-Analysis, Neurogastroenterology & Motility 18 (10): 927–935 (2006). The highest burst pressure obtained among the zein-based adhesives was Z40T7.
[0225] heart
[0226] Fig.11The burst pressure data of zein-based tissue sealants on porcine heart tissue at two different curing times are shown. The burst pressures of Z40T7 at 30 minutes and 2 hours were 0.58 ± 0.20 psi and 1.02 ± 0.29 psi, respectively. The burst pressures of Z40T7 + TGnase at 30 minutes and 2 hours of curing were 1.49 ± 1.21 psi and 1.8 ± 0.56 psi, respectively. The burst pressures of Z26T21 at 30 minutes and 2 hours of curing were 1.14 ± 0.46 psi and 1.19 ± 0.08 psi, respectively. The burst pressures of Z26T21 + TGnase at 30 minutes and 2 hours of curing were 1.72 ± 0.91 psi and 1.84 ± 0.62 psi, respectively. The burst pressures of Tisseel at 30 minutes and 2 hours of curing were 1.02 ± 0.79 psi and 1.59 ± 0.94 psi, respectively. The burst pressure of Superglue at 30 minutes and 2 hours of curing time was 3.85 ± 0.58 psi and 3.77 ± 0.74 psi, respectively.
[0227] All zein-based sealants tested outperformed Tisseel on cardiac tissue at both cure times. All sealants failed. In addition, the highest pressure in the human heart is the peak systolic pressure of the left ventricle and brachial artery, which is approximately 2.30 psi, which is higher than the values of zein-based sealants and the commercial fibrin sealant Tisseel. Reichek & Devereux, Reliable Estimation of Peak Left Ventricular Systolic Pressure by M-Mode Echographic-Determined End-Diastolic Relative Wall Thickness: Identification of Severe Valvular Aortic Stenosis in Adult Patients, Am Heart J 103(2): 202–209(1982). Z26T21+TGnase obtained the highest burst pressure.
[0228] Stomach
[0229] Fig.12The burst pressure data of zein-based tissue sealants on porcine stomach tissue at two different curing times are shown. The burst pressures of Z40T7 at 30 minutes and 2 hours of curing time are 1.22 ± 0.23 psi and 0.59 ± 0.08 psi, respectively. The burst pressures of Z40T7 + TGnase at 30 minutes and 2 hours of curing time are 0.69 ± 0.11 psi and 2.53 ± 1.01 psi, respectively. The burst pressures of Z26T21 at 30 minutes and 2 hours of curing time are 1.23 ± 0.63 psi and 0.63 ± 0.18 psi, respectively. The burst pressures of Z26T21 + TGnase at 30 minutes and 2 hours of curing time are 1.4 ± 0.53 and 1.49 ± 0.47 psi, respectively. The burst pressures of Tisseel at 30 minutes and 2 hours of curing time are 1.81 ± 1.51 psi and 1.48 ± 0.74 psi, respectively. The burst pressure of Superglue at 30 minutes and 2 hours of curing time was 5.73 ± 2.71 psi and 7.43 ± 0.78 psi, respectively. Adhesion failure was observed for all sealants. In addition, the normal pressure in the human stomach is approximately 0.23 psi, which is much lower than the value for the zein-based sealants tested, even at a short curing time of 30 minutes. The highest burst pressure was obtained for Z40T7+TGnase. Rooban et al. (2012), supra; Hamoud et al. (2021), supra.
[0230] lung
[0231] Fig.13 The burst pressure data of zein-based tissue sealants on porcine lung tissue at two different curing times are shown. The burst pressures of Z40T7 at 30 minutes and 2 hours of curing time are 0.62 ± 0.38 psi and 0.23 ± 0.06 psi, respectively. The burst pressures of Z40T7 + TGnase at 30 minutes and 2 hours of curing time are 0.37 ± 0.1 psi and 0.41 ± 0.08 psi, respectively. The burst pressures of Z26T21 at 30 minutes and 2 hours of curing time are 0.87 ± 0.21 psi and 0.22 ± 0.03 psi, respectively. The burst pressures of Z26T21 + TGnase at 30 minutes and 2 hours of curing time are 0.49 ± 0.07 and 0.64 ± 0.26 psi, respectively. The burst pressures of Tisseel at 30 minutes and 2 hours of curing time are 0.4 ± 0.15 psi and 0.59 ± 0.16 psi, respectively. The burst pressure of Superglue at 30 minutes and 2 hours of curing time was 0.82 ± 0.16 psi and 0.79 ± 0.34 psi, respectively.
[0232] All zein-based sealants tested performed better than Tisseel on lung tissue at both cure times. Adhesion failure was observed for all sealants. In addition, the normal pressure of the human lung is about 0.06 psi, which is much lower than the value of the zein-based sealants tested, even at the short cure time of 30 minutes. Zielinska-Krawczyk et al., Pleural Manometry–Historical Background, Rationale for Use and Methods of Measurement, Respiratory Medicine 136:21–28 (2018). The highest burst pressure was obtained with Z26T21+TGnase.
[0233] liver
[0234] Fig.14 The burst pressure data of liver of zein-based tissue sealants at two different curing times are shown. The burst pressure of Z40T7 at 30 minutes and 2 hours of curing time is 0.58 ± 0.1psi and 0.39 ± 0.1psi, respectively. The burst pressure of Z40T7 + TGnase at 30 minutes and 2 hours of curing time is 0.28 ± 0.05psi and 0.42 ± 0.14psi, respectively. The burst pressure of Z26T21 at 30 minutes and 2 hours of curing time is 0.54 ± 0.10psi and 0.54 ± 0.07psi, respectively. The burst pressure of Z26T21 + TGnase at 30 minutes and 2 hours of curing time is 0.34 ± 0.03psi and 0.55 ± 0.12psi, respectively. The burst pressure of Tisseel at 30 minutes and 2 hours of curing time is 0.13 ± 0.09psi and 0.03 ± 0.02psi, respectively. The burst pressure of Superglue at 30 minutes and 2 hours of curing time is 0.35 ± 0.18 psi and 0.84 ± 0.25 psi respectively.
[0235] All zein-based sealants tested performed better than Tisseel on liver tissue at both cure times. All sealants experienced bond failure. The liver is a highly vascularized organ with blood flow from the hepatic vein, portal vein, and artery. 75%-80% of the liver's blood supply is through the portal vein, which carries partially deoxygenated blood leaving the stomach, spleen, large and small intestines, pancreas, and gallbladder. The remaining 25% of blood flow can be attributed to the hepatic artery, which carries well-oxygenated blood.
[0236] Blood pressure in the human hepatic artery was similar to normal blood pressure, at 2.3 psi, which is higher than the burst pressure of any sealant reported herein. However, blood pressure in the portal vein was lower, at approximately 0.15 psi, lower than the values for the zein-based sealants tested, even at a short curing time of 30 minutes. Eipel et al., Regulation of Hepatic Blood Flow: The Hepatic Arterial Buffer Response Revisited, World J Gastroenterology: WJG 16(48): 6046-6057 (2010); Blumgart et al., Liver Blood Flow: Physiology, Measurement, and Clinical Relevance, Surgery Liver, Biliary Tract & Pancreas 1: 37–53 (2007).
[0237] Z40T7 achieved the highest burst pressure.
[0238] Aorta
[0239] Fig.15 The burst pressure data of zein-based tissue sealants on the aorta at two different curing times are shown. The burst pressure of Z40T7 at 30 minutes and 2 hours of curing time is 0.69 ± 0.54 psi and 0.87 ± 0.56 psi, respectively. The burst pressure of Z40T7 + TGnase at 30 minutes and 2 hours of curing time is 0.68 ± 0.26 psi and 1.26 ± 0.42 psi, respectively. The burst pressure of Z26T21 at 30 minutes and 2 hours of curing time is 1.81 ± 0.81 psi and 1.65 ± 0.35 psi, respectively. The burst pressure of Z26T21 + TGnase at 30 minutes and 2 hours of curing time is 0.69 ± 0.26 psi and 2.09 ± 0.52 psi, respectively. The burst pressure of Tisseel at 30 minutes and 2 hours of curing time is 2.89 ± 0.94 psi and 4.19 ± 0.71 psi, respectively. The burst pressure of Superglue at 30 minutes and 2 hours of curing time was 6.08±5.58 psi and 8.2±3.13 psi, respectively.
[0240] At both cure times, Tisseel outperformed all zein-based sealants tested on aortic tissue. All sealants exhibited adhesive failure except Tisseel, which exhibited cohesive failure. In addition, the normal pressure in the human aorta is approximately 2.3 psi, which is higher than the value for the zein-based sealants tested. Homan et al., Physiology, Pulse Pressure. Stat Pearls (2021). Z40T7 achieved the highest burst pressure.
[0241] Dura mater
[0242] Fig.16A and 16B The burst pressure data of all zein-based tissue sealants on the dura mater at two different curing times are shown. The burst pressure of Z40T7 at 30 minutes and 2 hours of curing time is 0.27 ± 0.13 psi and 1.47 ± 1.15 psi, respectively. The burst pressure of Z40T7 + TGnase at 30 minutes and 2 hours of curing time is 0.13 ± 0.04 psi and 0.74 ± 0.37 psi, respectively. The burst pressure of Z26T21 at 30 minutes and 2 hours of curing time is 0.46 ± 0.26 psi and 0.98 ± 0.6 psi, respectively. The burst pressure of Z26T21 + TGnase at 30 minutes and 2 hours of curing time is 0.58 ± 0.22 psi and 1.3 ± 0.32 psi, respectively.
[0243] All zein-based sealants exhibited adhesive-type failure. In addition, the normal pressure in the dura mater was approximately 0.34 psi, which is higher than the values for the zein-based sealants tested. Rangel-Castillo et al. (2008), supra. The highest burst pressure was obtained for Z40T7.
[0244] In conclusion, the zein-based sealants did not perform similarly on all tissue substrates. Furthermore, each of the four sealants performed best on a different tissue substrate. This suggests that the adhesion between the sealant and the target tissue is greatly influenced by the composition of the sealant and the tissue itself. Another important consideration is to match the mechanical properties of the sealant, such as elastic modulus or stiffness, to the underlying tissue.
[0245] In the short curing time of 30 minutes, Z26T21+TGnase, Z40T7, Z26T21+TGnase, Z26T21+TGnase, Z26T21+TGnase, Z40T7, Z26T21, Z26T21+TGnase and Z40T7 showed the highest burst pressure on skin, casing, stomach, heart, lung, liver, aorta, dura mater and small intestine, respectively. For the curing time of 2 hours, Z40T7, Z40T7, Z40T7+TGnase, Z26T21+TGnase, Z26T21+TGnase, Z26T21+TGnase, Z26T21+TGnase, Z40T7 and Z26T21 showed the highest burst pressure on skin, casing, stomach, heart, lung, liver, aorta, dura mater and small intestine, respectively. In most cases, the sealant that exhibited the highest burst pressure at 30 minutes of cure time (i.e., when the sealant was partially cured) was not the sealant that exhibited the highest burst pressure at full cure (i.e., 2 hours). This may be due to changes in the interaction between the sealant and tissue at longer cure times or due to changes in the mechanical properties of the sealant with cure time.
[0246] In addition, in the case of some tissues such as stomach, lung, and liver, the burst pressure of some sealants at 30 minutes of curing time was higher than that at 2 hours of curing time. This may be due to the mismatch between the mechanical properties of the sealant and the mechanical properties of the tissue after full curing at 2 hours. This mechanical difference between the sealant and the underlying tissue may lead to mechanical stress concentration at the tissue-sealant interface, thereby destroying the chemical and physical connection between them, resulting in delamination or failure. Example 13 Lap shear strength on porcine tissue substrates
[0247] The lap shear strength of all zein-based sealants was tested on porcine tissue substrates at two different curing times of 30 min and 2 h. The lap shear strengths of Z40T7 at 30 min and 2 h were 5.11 ± 2.75 kPa and 31.38 ± 13.74 kPa, respectively. The lap shear strengths of Z40T7+TGnase at 30 min and 2 h were 12.37 ± 1.75 kPa and 40.85 ± 13.92 kPa, respectively. The lap shear strengths of Z26T21 at 30 min and 2 h were 8.22 ± 0.31 kPa and 35.45 ± 7.32 kPa, respectively. The lap shear strengths of Z26T21+TGnase at 30 min and 2 h were 14.28 ± 3.16 kPa and 46.5 ± 15.94 kPa, respectively.
[0248] All sealants experienced adhesive failure. Z26T21+TGnase achieved the highest lap shear adhesion strength value on the porcine skin tissue substrate, while Z40T7 achieved the highest burst pressure (see Fig.17 ). Embodiment 14 Comparison of Zein-Based Sealants with Commercially Available Tisseel and Super Glue
[0249] It was observed that the zein-based sealants performed better than Tisseel on all tissue substrates, except for aortic tissue (in which case Tisseel performed much better than all zein-based sealants). Tisseel, a fibrin-based sealant, is a two-component sealant that involves the binding of purified fibrinogen and thrombin in the presence of calcium ions and factor XIII or transglutaminase. Activated factor XIII or TGnase catalyzes the formation of amides between the gamma-carboxamide of glutamine and the epsilon-amino groups of lysine on glutamine of fibrin polymers (formed by the conversion of thrombin-activated fibrinogen into fibrin monomers and subsequent self-assembly into fibrin polymers by hydrogen bonding) and tissue.
[0250] It is hypothesized that the reason Tisseel performed better on aortic tissue compared to any other tissue studied may be due to the greater availability of all the components that contribute to the formation of a fibrin sealant in aortic tissue (which itself transports blood in the body).
[0251] SuperGlue is a cyanoacrylate-based sealant that outperforms all zein-based sealants and Tisseel. Due to the high electronegativity of the alkoxycarbonyl and nitrile groups on the cyanoacrylate monomers, the unsaturated carbon double bonds on the acrylate monomers are electronically polarized and undergo Michael addition reactions with weak bases such as water and amines on the tissue. Although they have strong adhesion to most tissues, the mechanical difference between this extremely hard sealant and the soft underlying tissue poses a risk of tissue damage. In addition, Super Glue also decomposes into cytotoxic products including formaldehyde. For at least these reasons, Super Glue is not widely used in the medical / surgical field.
[0252] Additionally, it is noteworthy that the burst pressure trends across various tissues were fairly similar for all sealants studied (including Tisseel and Super Glue). For example, even a strong adhesive like SuperGlue showed lower burst pressure values for softer tissues (such as liver and lung tissue) compared to the burst pressure values on harder tissues like skin and stomach (similar to all other sealants tested). Embodiment 15 Bursting pressure of porcine small intestine
[0253] Fig. 22 The burst pressure data for all sealants studied on porcine small intestine at two different cure times are shown. The burst pressures of Z40T7 at 30 minutes and 2 hours of cure time were 0.25 ± 0.15 psi and 0.82 ± 0.36 psi, respectively. The burst pressures of Z40T7 + TGnase at 30 minutes and 2 hours of cure time were 1.25 ± 0.72 psi and 2.28 ± 0.38 psi, respectively. The burst pressures of Z26T21 at 30 minutes and 2 hours of cure time were 0.87 ± 0.39 psi and 0.79 ± 0.21 psi, respectively. The burst pressures of Z26T21 + TGnase at 30 minutes and 2 hours of cure time were 0.55 ± 0.42 psi and 0.55 ± 0.38 psi, respectively. The burst pressures of Tisseel at 30 minutes and 2 hours of cure time were 1.55 ± 0.32 psi and 0.40 ± 0.11 psi, respectively. With the exception of Z26T21, which exhibited cohesive failure at 30 minutes of cure time, and Tisseel, which exhibited cohesive failure at both cure times, all other sealants exhibited adhesive failure. Furthermore, the normal pressure in the small intestine is approximately 0.38 psi, which is higher than the values for the zein-based sealants studied in this paper. The highest burst pressure was obtained for Z40T7+TGnase. Example 16 Further lap shearing studies on various zein to TA ratios
[0254] To further determine the optimal zein and TA concentrations for the sealant, lap shear tests similar to the study of Example 5 were performed for various zein and TA ratios. Here, the zein percentage varied from 26-45 wt % and the TA percentage varied from 1-28 wt %. Formulations with lower amounts of zein and TA had low viscosity and no tack and were therefore excluded from the study. Some formulations with higher amounts of zein and TA were also not studied due to extremely high viscosity and low tack.
[0255] Based on the above, 17 formulations were identified and investigated for lap shear adhesion strength on porcine skin tissue. The adhesives were cured in a humid environment at 37°C for 2 hours. Fig.23The lap shear adhesion strength of all test preparations is shown. The adhesion strength of all zein adhesives is higher than the normal intra-abdominal pressure (IAP) of humans. When using 26 wt % zein, 28 wt % TA loads result in the highest lap shear strength. When using 30 wt % zein, 21 wt % TA loads result in the highest lap shear strength. When using 35 wt % zein, 14 wt % TA loads result in the highest lap shear strength. When using 40 wt % zein, 7 wt % TA loads result in the highest lap shear strength. When using 45 wt % zein, 7 wt % TA loads result in the highest lap shear strength. In general, when 26 wt % zein is mixed with 28 wt % TA, the highest lap shear strength is obtained.
[0256] The lap shear strength of an FDA-approved fibrin-based tissue sealant at two different cure times was also studied, as shown below in Table 1. No statistical differences were found in the adhesion strength at the two cure times with the adhesive formulations of the present disclosure tested. Table 1. Lap shear strength of FDA-approved tissue sealants (ARTISS) at different curing times Curing time Lap shear strength(kPa) 30 minutes 18.5±8.09 2 hours 13.60±5.39
[0257] Fig.24 A comparison of the lap shear strength of ARTISS and the zein-based adhesives herein at 2 hours of cure time is shown. The adhesion strength of ARTISS is not only lower than at least formulations Z26T28, Z30T21 and Z40T7, but is also well below the maximum intra-abdominal pressure experienced by humans when jumping. Embodiment 17 Cytocompatibility studies
[0258] NIH 3T3 fibroblasts were cultured in high glucose Dulbecco's modified Eagle's medium (DMEM) containing 10% fetal bovine serum (Lonza, Basel, Switzerland) and 1% penicillin / streptomycin antibiotics. Subcultures were performed every 3 days or when the cell confluence was ≥ 60%. The cytocompatibility of the zein-based sealants was investigated by culturing cells in sealant extracts according to ISO 10993-5.
[0259] Briefly, 200 μl of sealant was cured in a humidified environment at 37°C for 72 hours to form cylindrical samples. The samples were then immersed in 5 ml of DMEM for 24 hours to obtain the leachate. The leachate was studied at three different dilutions: 1X, 10X, and 100X. The leachate was sterile filtered using a 0.2 μm filter. Cells were plated at 5000 cells / cm 2 Seed onto PLL-coated coverslips and incubate overnight. After cell attachment, replace medium with 500 μl of diafiltration solution. Incubate cells in diafiltration solution for 24 hours.
[0260] To measure viability, a live / dead assay was used. Cells were rinsed with PBS containing 0.01 wt% calcium chloride and 0.01 wt% magnesium chloride (PBS+) to prevent shedding. Negative control samples were incubated with 70% ethanol at room temperature for 5 minutes. Samples were stained with calcein-acetoxymethyl and ethidium homodimer (LIVE / DEAD Viability / Cytotoxicity kit, Thermo Fisher, Waltham, MA) at 37°C for 30 minutes, rinsed and mounted on microscope slides. Fluorescence images were obtained with excitation at 495 nm and emission at 532 nm.
[0261] Metabolic activity was assessed using the PrestoBlue assay (Thermo Fisher, Waltham, MA). Cells on PLL-coated coverslips served as positive controls, and uncoated, cell-free glass coverslips served as background controls. After incubation, three aliquots were removed and placed in 96-well plates. Fluorescence of the reagents was measured using 555 nm excitation and 595 nm emission.
[0262] like Fig.25A and 25B As shown, Z40T7 showed cell viability at all leachate concentrations, while Z26T21 showed viability only when the leachate was diluted 10-fold and 100-fold. Fig.25C The PrestoBlue assay results shown support that the cell metabolic activity of both Z40T7 and Z26T21 increased with increasing dilution of the filtrate. The low cell viability and metabolic activity may be due to the catechol groups in TA, which lead to the generation of reactive oxygen species (ROS). Embodiment 18 Gamma irradiation of sealants for in vivo studies
[0263] In order for the sealants to be usable in vivo, it is useful for the sealants to withstand sterilization. For example, in order to study the wound healing ability of these sealants in vivo, they must first be sterilized using a suitable method. Gamma irradiation was chosen as the sterilization method.
[0264] The sealants were exposed to gamma irradiation up to 30 kGy. The burst pressure of the sealants was then tested by curing them on casings for 30 minutes. The burst pressure of Z40T7 dropped slightly from 1.63 ± 0.47 psi to 0.97 ± 0.26 psi ( Fig.26 ). However, for Z26T21, the burst pressures before and after gamma ray irradiation were very similar. Embodiment 19 In vivo wound healing study in rats
[0265] The in vivo wound healing ability of zein-based sealants was studied on the dorsal skin of male Sprague Dawley (SD) rats. The experiment consisted of 4 test articles: Z40T7 sealant, Tisseel, sutures, and Z40T7 sealant + sutures. The wound healing of rats was studied at different time points of 7 and 14 days, with n=4 rats studied at each time point.
[0266] In brief, the hair on the back was removed to expose the skin. Four equidistant 1 cm long incisions were made on the rat back skin, and each of the four test articles was applied to each wound. The surgery was performed under general anesthesia (isofluorane). The weight and activity level of the rats were recorded regularly at the beginning of the experiment and during the experiment. The injury site was checked for signs of irritation, and photos of the injury site were taken on the 0th, 4th, 7th, 10th and 14th days to determine the wound closure rate. At the end of each time point of the study, the rats were euthanized. The tissue of the injury site was harvested and further processed for histopathological analysis.
[0267] Fig. 27 Photographs showing the application of the four test articles to all rats during the 7-day study are shown. In all cases, the wound area decreased over time. In some cases, the healing process was accompanied by scab formation around the wound without any complications. Furthermore, in the Z40T7+suture group, the sealant remained adhered to the wound even at the end of the 7th day.
[0268] Fig.28Photos of all rats treated with the four test articles over a 14-day study are shown. In all cases, the wounds were almost completely healed by day 14. The suture-only group had completely healed wounds at day 10, while the Z40T7-only group had completely healed wounds at day 14. In the Tisseel-only group, all mice had healed wounds except for one mouse that still had some scabs at day 14. The Z40T7+suture group also had scabs and swelling from the injected adhesive. Embodiment 20 Feasibility of using a zein-based adhesive in combination with graft material as a tissue adhesive for sealing dural perforations
[0269] Different zein-based adhesives have been assessed for their adhesion strength when used as adhesives that graft materials are bonded to the dura mater. Initially, sausage casing and collagen casing were used as model tissue and graft materials, respectively. 1 cm perforations were made on the casing. A 2*2 cm collagen casing was placed on the top of the casing, and zein adhesive (Z40T7 and Z26T21) was used to seal the edges. The adhesive was cured for 30 minutes, and then the burst pressure was studied. Fig.29 The burst pressures of both adhesives are shown, both being 0.34 psi above normal intracranial pressure.
[0270] Thereafter, the application of the adhesive was modified to simulate real-time application by applying the adhesive on top of the graft rather than only at the edges. The curing time was also shortened to 15 minutes. The three zein formulations (zein alone (without TA), Z40T7, and Z26T21) were applied alone and in combination with transglutaminase powder (TGnase). Only Z40T7+TGnase showed adhesion strength above intracranial pressure ( Fig.30 ).
[0271] Next, burst pressure was evaluated to investigate the adhesion strength when the adhesive was applied to the dura mater in combination with a commercial graft compared to a gut-coated with a collagen-coated graft.In each case, the adhesive was applied over the entire graft material and allowed a 15-minute curing time.
[0272] Fig.31 The burst pressures of Z40T7+Tgnase when applied to the dura mater and the graft are shown. The burst pressures are much lower than those obtained when the casing is adhered to the collagen casing. These values are also lower than normal intracranial pressure.
[0273] To standardize the test and reduce the variability caused by use, the adhesive was then applied only directly on the 2*2.5 cm size graft and pressed against the 1 cm perforation on the dura, or the adhesive could be applied directly to a 2*2.5 cm area around the perforation and a graft piece of the same size applied on top of the adhesive. Approximately 80 μl of adhesive was used. Fig.32 As shown, the adhesion strength was higher when the adhesive was first applied to the graft for a 15 minute curing time. When the curing time was increased to 40 minutes, the adhesion strength increased further.
[0274] like Fig.33 As shown, when used on the dura, the adhesive volume was increased from 80 μl to 150 μl. This resulted in an increase in adhesive strength, especially for Z26T21, even at a 15-minute curing time. The adhesive volume used on the graft remained the same at 80 μl. The adhesive strength of Z26T21 was higher than the intracranial pressure.
[0275] The effect of transglutaminase addition on burst pressure was also investigated. 150 μl of transglutaminase solution was first applied to the dura, followed by 150 μl of zein-based adhesive. Curing time was 15 minutes at room temperature. When transglutaminase was applied, the adhesion strength was greatly reduced ( Fig.34 ).
[0276] like Fig.35 As shown, the curing time increased from 15 minutes to 30 minutes and 2 hours. For Z40T7, the burst pressure increased from 0.09 psi at 15 minutes to 0.18 psi and 0.19 psi at 30 minutes and 2 hours, respectively. For Z26T21, the burst pressure did not show any significant change with the increase in curing time; however, all values for Z26T21 were above the intracranial pressure, which was not the case for Z40T7.
[0277] Next, the effect of reducing the perforation size from 10 mm to 5 mm was evaluated. Fig.36 As shown in Figure 2, the size of the graft used as a cover graft was also reduced accordingly. The burst pressure decreased when the perforation size was reduced, which was contrary to expectation. Therefore, it was assumed that the perforation size would not have a great influence on the burst pressure intensity as long as the bonding area between the dura mater and the graft was high enough.
[0278] The lap shear adhesion strength of the dura mater bonded to the graft was also assessed at different curing times. The dura mater and graft were cut into 1.5*1.2 cm slices and bonded to an aluminum substrate using super glue. 30 μl of Z40T7 or Z26T21 were applied to the dura mater and the graft, which were overlapped to form a lap shear joint. A 50 gram lead block was placed on the top to improve the contact between the two overlapping surfaces.
[0279] The adhesion strength of Z40T7 increased from 19.73±11.43psi at 15 minutes to 31.53±12.23psi at 30 minutes. The adhesion strength of Z26T21 increased from 7.77±4.49psi at 15 minutes to 21.29±19.92psi at 30 minutes. Fig.37 As shown, Z40T7 has the highest adhesion strength, although Z26T21 records the highest burst pressure. Embodiment 21 Adhesion study of hydroxyapatite
[0280] The adhesion strength of Z40T7 and Z26T21 formulations on hydroxyapatite (HAP) substrates was further studied to examine their feasibility for application in an oral environment. HAP substrates were immersed in PBS for 5 minutes or in saliva (to form a biofilm). 20 μl of adhesive was applied to the HAP tiles using a spatula. The adhesive was allowed to cure for 10 minutes under ambient conditions. A commercial water floss (Waterpik Ultra) was rastered over the coating for 1 minute to study the adhesion of the coating. The water floss tip was set at a constant height of 1 mm from the substrate. Images of the substrates before and after the water floss test were taken to analyze the amount of adhesive remaining on the substrate after the test. Fig.38 Some representative images of adhesive coatings on HAP substrates before and after water floss testing are shown. Z40T7 was observed to adhere more strongly to HAP than Z26T21. The adhesion strength appeared to be similar whether the substrate was soaked in PBS or biofilm. Embodiment 22 HAP basal staining study
[0281] To improve the contrast of the ImageJ analysis of HAP substrates, Coomassie Brilliant Blue stain (a mixture of water, acetic acid, methanol, and Coomassie Brilliant Blue) was used. Fig.39 As shown, it was found that leaving the substrate for 7 hours followed by destaining with a destaining solution (a mixture of water, acetic acid and methanol) for 24 hours gave the best contrast in the control sample.
[0282] To be able to reuse the HAP disk, soak the used disk in 12M HCl for 5 minutes to clean the surface. Hydrochloric acid (HCl) will dissolve the HAP, which will cause the disk surface to become rougher due to etching by the HCl. Soak the disk in simulated saliva for 5 minutes. Clean the excess saliva on the disk surface, and then apply Z40T7 and Z26T21 to the disk. Then cure the disk in the saliva for 10 minutes. Fig.40 As shown, the disks cleaned with HCl had good adhesion to the zein adhesive, while brand new disks with a smoother surface showed poor adhesion. Embodiment 23 Study on the Adhesion of Limestone (Effect of Curing in Air and in Saliva)
[0283] The adhesion of the adhesive coating on a limestone substrate was also studied. Prior to applying the adhesive, the substrate was immersed in simulated saliva for 5 minutes. 20 μl of adhesive was applied to the substrate using a spatula. The adhesive was allowed to cure in air or in simulated saliva for 10 minutes. A commercial water flosser (Waterpik Ultra) was scanned over the coating for 1 minute to study the adhesion of the coating. The water flosser tip was set at a constant height of 1 mm from the substrate. Images of the substrate before and after the water flossing test were taken to analyze the amount of adhesive remaining on the substrate after the test. Fig.41 The percentage of coating remaining after water flossing tests at different pressure settings is shown. It is observed that the adhesive retention after the water flossing experiment is better for Z26T21 even at high pressure. Furthermore, adhesion is even better when the substrate is cured under saliva rather than in air. Embodiment 24 Study on Adhesion of Hydroxyapatite Coated Glass
[0284] Adhesion of the adhesive coatings to hydroxyapatite-coated glass substrates was also investigated. The coatings were cured under saliva for 10 minutes and tested at a pressure of 5. Coating retention was poor when the adhesive was applied in thicker layers, but much better when the adhesive was applied in thinner layers, as shown in Figure 2. Fig.42 shown.
[0285] The effect of adding hydroxyapatite powder as a filler to Z26T21 was also evaluated. The filler content varied from 1 to 20 wt%. Fig.43 As shown, adhesion is better at lower filler content. At higher filler content, the coating suffers from cohesive failure.
Claims
1. An adhesive comprising zein and one or more catechol- or gallol-containing compounds, wherein optionally, prior to curing, the zein comprises at or about 25-45 weight percent of the adhesive.
2. The adhesive according to claim 1, further comprising an interfacial crosslinking agent, an iron crosslinking agent, or both an interfacial crosslinking agent and an iron crosslinking agent.
3. The adhesive of claim 1, wherein the one or more catechol- or gallol-containing compounds comprises catechol, vanillin, caffeic acid, juglone (5-hydroxy-1,4-naphthoquinone), catecholamines, resveratrol, 3,4-dihydroxyphenylacetic acid (DOPAC), catechin hydrate, 3,4-dihydroxybenzoic acid, 3,4-dihydroxybenzaldehyde, tannic acid (TA), gallic acid, gallic tannin, ellagic acid, pyrogallol acetate, 1,2,3-trihydroxybenzene, quercetin, gallol, or any combination thereof.
4. The adhesive of any one of claims 1-3, formulated at a pH of 6-8 or about 6-8.
5. The adhesive according to any one of claims 1 to 3, formulated at or about neutral pH (pH=7).
6. The adhesive according to claim 2, wherein the adhesive comprises an interfacial crosslinker, and the interfacial crosslinker comprises transglutaminase (TGnase), ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), N-hydroxysuccinimide (NHS), elastin-like polypeptide (ELP), polyethylene glycol (PEG), dendrimers, glutaraldehyde and / or a photocrosslinker.
7. The adhesive according to any one of claims 2, 3 or 6, wherein the adhesive comprises an interfacial crosslinking agent containing TGnase.
8. The adhesive of claim 3, wherein zein comprises at or about 25 to 45 weight percent and the one or more catechol- or gallol-containing compounds is tannic acid, which comprises at or about 5 to 30 weight percent of the uncured adhesive.
9. The adhesive of claim 3, wherein zein comprises at or about 40 weight percent and the one or more catechol- or gallol-containing compounds is tannic acid, which comprises at or about 7 weight percent of the uncured adhesive.
10. The adhesive of claim 3, wherein zein comprises at or about 26 weight percent and the one or more catechol- or gallol-containing compounds is tannic acid, which comprises at or about 21 weight percent of the uncured adhesive.
11. The adhesive of claim 3, wherein zein comprises at or about 26 weight percent and the one or more catechol- or gallol-containing compounds is tannic acid, which comprises at or about 28 weight percent of the uncured adhesive.
12. The adhesive of claim 3, wherein zein comprises at or about 30 weight percent and the one or more catechol- or gallol-containing compounds is tannic acid, which comprises at or about 21 weight percent of the uncured adhesive.
13. The adhesive according to claim 1, further comprising a solvent.
14. The adhesive of claim 13, wherein the solvent is an aqueous solvent, an organic solvent, or both an aqueous and an organic solvent.
15. The adhesive of claim 13, wherein the solvent comprises ethanol and water.
16. The adhesive of claim 15, wherein the ethanol and water are present in a volume ratio of (2-5):1 or about (2-5):
1.
17. The adhesive of any one of claims 1-3 and 6-16 having a tensile strength of up to about 20 MPa.
18. The adhesive of any one of claims 1-3 and 6-16, further comprising at least one filler.
19. The adhesive of claim 18, wherein the at least one filler comprises hydroxyapatite, calcium carbonate, calcium phosphate, magnesium phosphate, laponite, montmorillonite, or any combination thereof.
20. The adhesive of claim 2, wherein the adhesive comprises an iron crosslinking agent, the iron crosslinking agent comprising ferrous sulfate (FeSO4), ferric chloride (FeCl3), iron oxide nanoparticles, ferric nitrate (Fe(NO3)3), iron (III) acetylacetonate (Fe(acac)3 or Fe(C5H7O2)3), potassium ferrate (K2FeO4), or any combination thereof.
21. A tissue sealant comprising zein, tannic acid and a solvent.
22. The tissue sealant of claim 21, wherein the solvent comprises an aqueous solvent, an organic solvent, or both an aqueous solvent and an organic solvent.
23. The tissue sealant of claim 21, wherein the solvent comprises ethanol and water.
24. The tissue sealant according to any one of claims 21 to 23, which consists of zein, tannic acid, ethanol and water.
25. The tissue sealant of claim 21, further comprising an interfacial crosslinking agent, an iron crosslinking agent, or both an interfacial crosslinking agent and an iron crosslinking agent.
26. The tissue sealant of claim 25, wherein the interfacial cross-linking agent comprises transglutaminase (TGnase).
27. The tissue sealant of claim 21, 26 or 27 further comprising at least one filler.
28. The tissue sealant of claim 21, 26 or 27, further comprising at least one filler, wherein the at least one filler comprises hydroxyapatite, calcium carbonate, calcium phosphate, magnesium phosphate, laponite, montmorillonite or any combination thereof.
29. A method of sealing damaged tissue in a subject comprising applying the adhesive of any one of claims 1-20 or the tissue sealant of any one of claims 21-28 to the damaged tissue.
30. The method of claim 29, wherein the method further comprises: applying an interfacial crosslinker to the damaged tissue to form a first layer, and The adhesive or tissue sealant is applied to the first layer.
31. The method of claim 30, wherein the interfacial crosslinking agent comprises transglutaminase (TGnase), ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC), N-hydroxysuccinimide (NHS), elastin-like polypeptide (ELP), polyethylene glycol (PEG), dendrimers, glutaraldehyde and / or a photocrosslinker.
32. The method of claim 30, wherein the interfacial crosslinking agent comprises TGnase powder.
33. The method of claim 30, wherein the interfacial crosslinking agent comprises a viscous solution containing TGnase and water.
34. The method of any one of claims 29-33, wherein the damaged tissue is selected from the group consisting of skin, cardiac tissue, stomach tissue, lung tissue, liver tissue, intestine, dura mater, and aorta.
35. The method of claim 29, wherein the damaged tissue is located in an oral environment.
36. The method of claim 35, further comprising curing the adhesive or sealant in saliva.
37. The method of claim 35, further comprising curing the adhesive or sealant in the presence of a biological fluid.
38. The method of any one of claims 29-33, wherein the subject is a mammal.
39. The method of claim 29, wherein the one or more catechol- or gallol-containing compounds interact with functional groups of the damaged tissue to promote adhesive bonding to the damaged tissue.
40. The method of claim 29, further comprising applying suture to the damaged tissue.
41. The method of claim 29, further comprising administering a graft to the damaged tissue.
42. The method of claim 41, wherein the adhesive or tissue sealant is first applied to the graft, and the adhesive or tissue sealant and graft are applied to the damaged tissue.
43. The method of claim 42, further comprising allowing the adhesive or tissue sealant applied to the graft to cure for less than about 15 minutes prior to applying the adhesive or tissue sealant and graft to the damaged tissue.
44. The method of claim 29, further comprising curing the adhesive or tissue sealant by removing or facilitating removal of a solvent in the adhesive or tissue sealant.
45. The method of claim 44, wherein curing the adhesive or tissue sealant comprises exposing the adhesive or tissue sealant to oxygen and / or heat.
46. The method of claim 42, further comprising allowing the adhesive or tissue sealant applied to the graft to cure for less than about 40 minutes prior to applying the adhesive or tissue sealant and graft to the damaged tissue.
47. The method of claim 41, wherein the adhesive or tissue sealant is applied to the damaged tissue and then the graft is applied to the damaged tissue and the adhesive or tissue sealant.
48. The method of claim 41, wherein the graft is applied to the damaged tissue and the adhesive or tissue sealant is then applied in a layer over the surface of the graft and to the tissue surrounding the graft.
49. The method of any one of claims 29-33, 35-37, and 39-48, wherein the volume of the adhesive or tissue sealant applied is about 80 μl to 150 μl.
50. The method of any one of claims 29-33, 35-37, and 39-48, wherein the adhesive or tissue sealant is applied in a volume of about 10 μl to 25 ml.
51. The method of any one of claims 29-33, 35-37, and 39-48, wherein the adhesive or tissue sealant is applied in a volume at or about 150 μl.
52. A method of preparing an adhesive, comprising: forming a first solution by combining zein, one or more catechol- or gallol-containing compounds, a solvent, and optionally an interfacial crosslinking agent, an iron crosslinking agent, or both an iron crosslinking agent and an interfacial crosslinking agent; adjusting the pH of the first solution to at or about 6-8 (e.g., pH 6, pH 7, pH 8, or pH 6-8); and The first solution is solidified to substantially remove the solvent therefrom.
53. The method of claim 52, wherein solidifying the first solution comprises incubating the first solution at about 31.0°C to about 42.0°C.
54. The method of claim 52 or 53, wherein curing the first solution comprises exposing the first solution to oxygen.
55. The method of claim 52 or 53, wherein curing the first solution comprises photocuring and / or exposing the first solution to oxygen.
56. The method of claim 52, wherein the one or more catechol- or gallol-containing compounds comprises catechol, vanillin, caffeic acid, juglone (5-hydroxy-1,4-naphthoquinone), catecholamines, resveratrol, 3,4-dihydroxyphenylacetic acid (DOPAC), catechin hydrate, 3,4-dihydroxybenzoic acid, 3,4-dihydroxybenzaldehyde, tannic acid (TA), gallic acid, gallotannin, ellagic acid, pyrogallol acetate, 1,2,3-trihydroxybenzene, quercetin, gallol, or any combination thereof.
57. The method of claim 52, wherein the first solution further comprises TGnase.
58. The method of claim 52, further comprising applying the incubated first solution to the layer comprising TGnase.
59. The method of claim 58, wherein the TGnase is a powder.
60. The method of claim 58, wherein the TGnase is part of a viscous solution comprising TGnase and water.
61. The method of claim 52, wherein the solvent comprises ethanol and water, the solvent having a ratio of ethanol to water of about 5:1, about 4:1, about 3:1, or about 2:
1.
62. The method of claim 52, wherein the one or more catechol- or gallol-containing compounds of the first solution comprises tannic acid, the first solution comprising at or about 40 weight percent zein and at or about 7 weight percent tannic acid.
63. The method of claim 52, wherein the one or more catechol- or gallol-containing compounds of the first solution comprises tannic acid, the first solution comprising at or about 26 weight percent zein and at or about 21 weight percent tannic acid.
64. The method of claim 63, wherein the one or more catechol- or gallol-containing compounds of the first solution comprises tannic acid, the first solution comprising at or about 26 weight percent zein and at or about 28 weight percent tannic acid.
65. The method of claim 52, wherein the one or more catechol- or gallol-containing compounds of the first solution comprises tannic acid, the first solution comprising at or about 30 weight percent zein and at or about 21 weight percent tannic acid.
66. The method of claim 52, wherein the ratio of the amounts of zein, the one or more catechol- or gallol-containing compounds, and the solvent are adjusted to tune one or more properties of the adhesive to correspond to the mechanical properties of the target tissue.
67. The method of claim 66, wherein the one or more properties of the adhesive include modulus or stiffness.
68. A kit for preparing an adhesive or a tissue sealant, the kit comprising at least one of the adhesive according to claims 1-20 or the tissue sealant according to claims 21-28, and instructions for use.
69. The kit of claim 68, comprising zein, one or more catechol- or gallol-containing compounds, and a solvent, wherein the zein and one or more catechol- or gallol-containing compounds are hydrated by the solvent for immediate use.
70. The kit of claim 68, comprising zein, one or more catechol- or gallol-containing compounds, and a solvent, wherein the zein is hydrated by the solvent and stored in a first container and the one or more catechol- or gallol-containing compounds are stored in a second container.